Composite film with Anti-reflective coating

A composite film with a UV-curable acrylate binder and silica nanoparticles addresses the balance of high transmittance, low haze, and low reflectance, improving optical properties for medical and safety glass applications.

JP2025011159AInactive Publication Date: 2025-01-23SAINT GOBAIN PERFORMANCE PLASTICS CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024172561
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-06-20
Filing Date
2024-10-01
Publication Date
2025-01-23
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing composite films used as coatings on glass components do not effectively balance high visible light transmittance, low haze, and low reflectance, which are crucial for applications such as medical boards and safety glasses.

Method used

A composite film with a transparent substrate and an anti-reflective coating comprising a UV-curable acrylate binder, photoinitiator, and silica nanoparticles, with specific ratios and concentrations to achieve a VLT of about 93.0% and a haze value of about 3% or less.

Benefits of technology

The solution provides a composite film with enhanced optical properties, achieving high visible light transmittance, low haze, and low reflectance, suitable for medical and safety glass applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011159000003
    Figure 2025011159000003
  • Figure 2025011159000004
    Figure 2025011159000004
  • Figure 2025011159000005
    Figure 2025011159000005
Patent Text Reader

Abstract

To provide an improved composite film which exhibits a high visible light transmittance, low haze, and low reflectance.SOLUTION: A composite film may comprise a first transparent substrate and a first anti-reflective coating laminated on a first surface of the first transparent substrate. The first anti-reflective coating may contain a first UV curable acrylate binder, a photo initiator component, and silica nanoparticles dispersed within the first anti-reflective coating. The first anti-reflective coating may further have a ratio AC1SiO2 / AC1B in a range of at least about 0.01 to about 1.3 or less. The composite film may further have a VLT of at least about 93.0% and a haze value of about 3% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to composite films. In particular, the present disclosure relates to composite films having certain solar and optical properties. The present invention relates to a composite film having an antireflective coating with excellent antireflection properties. [Background technology]

[0002] Composite films are used as coatings applied to various glass components to protect the glass. It can strengthen and control the passage of solar radiation by transmission, reflection and absorption. Application materials and coating materials for medical glass components such as glasses, protective shields, and protective glasses In some composite film applications, the composite film has high visible light transmission ("VLT"), low This combination of features is required for a particular system. Therefore, the development of improved composite fillers for such applications is essential. There continues to be demand for the room. Summary of the Invention

[0003] According to a first aspect, the composite film comprises a first transparent substrate and a first surface of the first transparent substrate. The optical fiber may include a first anti-reflective coating disposed on the surface. The first anti-reflective coating may include a first ultraviolet (UV) curable acrylate binder, a photoinitiator component, and a first anti-reflective coating. The first antireflective coating may include silica nanoparticles dispersed in the coating. Ratio AC1 of at least about 0.01 and not more than about 1.3 SiO2 / AC1 B Further comprising AC1 SiO2 is the weight of the first anti-reflective coating relative to the total weight of the first anti-reflective coating. is the concentration by weight percent of silica nanoparticles in the protective coating; AC1 B The The weight ratio of the first U in the first antireflective coating to the total weight of the first antireflective coating V is the concentration in weight percent of the curable acrylate binder. The composite film is at least Both may further have a VLT of about 93.0% and a haze value of about 3% or less.

[0004] According to another embodiment, the composite film includes a first transparent substrate and a first The composite film may include a first anti-reflective coating laminated to a surface thereof. The antireflective coating comprises a first UV-curable acrylate binder, a photoinitiator component and The first antireflective coating may include silica nanoparticles dispersed therein. The coating is at least about 40% by weight based on the total weight of the first antireflective coating, and The first reaction mixture may include a first UV-curable acrylate binder at a concentration of about 95% by weight or less. The antireflective coating comprises at least about 2.5% by weight of the total first antireflective coating. The first antireflective coating may further include a photoinitiator component at a concentration of about 0% by weight and about 10% by weight or less. The antireflective coating comprises at least about 5% by weight based on the total weight of the first antireflective coating. and may also include silica nanoparticles at a concentration of up to about 60% by weight. The glass may further have a VLT of about 93.0% and a haze value of about 3% or less.

[0005] According to yet another aspect, a method of forming a composite film includes providing a first antireflective coating Providing a formulation; applying the first antireflective coating formulation to a transparent substrate; and drying the first anti-reflective coating formulation to form a first anti-reflective coating layer laminated on the transparent substrate. The first anti-reflective coating may include forming a composite film that may include an anti-reflective coating. The coating formulation comprises a first UV-curable acrylate binder component, a second photoinitiator component, and a third UV-curable acrylate binder component. The first antireflective coating formulation may include a first antireflective coating composition. A concentration of at least about 0.4% by weight and no more than about 5.5% by weight based on the total weight of the coating. The first anti-reflective coating may include a first ingredient UV curable acrylate binder component. The coating formulation is at least about 0.5 wt. The composition may further include a raw photoinitiator component at a concentration of about 2% by weight and up to about 2.0% by weight. The antireflective coating formulation comprises at least about 100% by weight of the first antireflective coating. The composite may also contain silica nanoparticles at concentrations up to about 0.7% by weight and up to about 1.9% by weight. The film may further have a VLT of at least about 93.0% and a haze value of about 3% or less. .

[0006] According to yet another aspect, a method of forming a composite film includes providing a first antireflective coating Providing a formulation; applying the first antireflective coating formulation to a transparent substrate; and drying the first anti-reflective coating formulation to form a first anti-reflective coating layer laminated on the transparent substrate. The first anti-reflective coating may include forming a composite film that may include an anti-reflective coating. The coating formulation comprises a first UV-curable acrylate binder component, a second photoinitiator component, and a third UV-curable acrylate binder component. The first antireflective coating formed by the method may include silica nanoparticles. The coating comprises a first UV-curable acrylate binder, a photoinitiator component, and a first anti-reflective coating. The first antireflective coating may comprise silica nanoparticles dispersed in the coating. Ratio AC1 of about 0.01 and about 1.3 or less SiO2 / AC1 B and may further include AC 1 SiO2 is the weight of the first antireflective coating relative to the total weight of the first antireflective coating. is the concentration of silica nanoparticles in the coating in weight percent, and AC1 B The first anti-reflective The weight of the first UV-curable active ingredient in the first antireflective coating relative to the total weight of the coating The composite film has a concentration of at least about 93. It may further have a VLT of 0% and a haze value of about 3% or less.

[0007] According to yet another aspect, a method of forming a composite film includes providing a first antireflective coating Providing a formulation; applying the first antireflective coating formulation to a transparent substrate; and drying the first anti-reflective coating formulation to form a first anti-reflective coating layer laminated on the transparent substrate. The first anti-reflective coating may include forming a composite film that may include an anti-reflective coating. The coating formulation comprises a first UV-curable acrylate binder component, a second photoinitiator component, and a third UV-curable acrylate binder component. The first antireflective coating formed by the method may include silica nanoparticles. The coating comprises a first UV-curable acrylate binder, a photoinitiator component, and a first anti-reflective coating. The first reflective layer formed by the method may include silica nanoparticles dispersed in the reflective layer. The antireflective coating has a weight of at least about 40% based on the total weight of the first antireflective coating. % by volume and at a concentration of up to about 95% by weight. The first antireflective coating formed by the method is a photoinitiator in a concentration of at least about 2.0% by weight and no more than about 10% by weight based on the total weight of the coating; The first antireflective coating formed by the method may further include a first component. At least about 5% by weight and no more than about 60% by weight based on the total weight of the antireflective coating of The composite film may also include silica nanoparticles at a concentration of at least about 93.0% VL T and a haze value of about 3% or less.

[0008] Embodiments are illustrated by way of example and not limitation in the accompanying figures. [Brief description of the drawings]

[0009] [Figure 1] 1 includes an illustration of an example composite film according to certain embodiments described herein. [Diagram 2] 2 includes an illustration of another example of a composite film according to certain embodiments described herein. [Diagram 3] 2 includes an illustration of another example of a composite film according to embodiments described herein. [Figure 4] 2 includes an illustration of another example of a composite film according to certain embodiments described herein. [Figure 5a] 2 includes an illustration of another example of a composite film according to certain embodiments described herein. [Figure 5b] 2 includes an illustration of another example of a composite film according to certain embodiments described herein. [Figure 6a] 2 includes an illustration of another example of a composite film according to certain embodiments described herein. [Figure 6b] 2 includes an illustration of another example of a composite film according to certain embodiments described herein.

[0010] Those skilled in the art will appreciate that elements in the figures are illustrated for simplicity and clarity and have not necessarily been drawn to scale. I am aware of this. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The following discussion focuses on specific implementations and embodiments of the teachings. It is provided to aid in the explanation of the embodiments and is not intended to limit the scope or applicability of the disclosure or teachings. Based on the disclosure and teachings provided herein, other implementations may be construed as being equivalent to the It is recognized that any state can be used.

[0012] "comprises", "comprising", "in "includes," "including," "has," "has The term "having" or any other variation is intended to include a non-exclusive inclusion. For example, a method, article, or apparatus that includes a list of features is not necessarily limited to only those features. Other characteristics not expressly recited or inherent in such method, article or apparatus are not specified herein. Further, unless expressly stated to the contrary, "or" is inclusive. indicates logical inclusive-or, and exclusive-or For example, condition A or B can be satisfied by one of the following: A is true A is (or exists) and B is false (or does not exist), A is false (or exists) A is not true (or exists) and B is true (or exists), and both A and B are true (or exist). exists).

[0013] Additionally, the use of "a" or "an" describes elements and components described herein. This is done merely for convenience and to give a general sense of the scope of the invention. This explanation is given for one purpose only, unless it is clear that it is meant otherwise. , at least one or the singular, and vice versa. For example, where a single item is described herein, more than one item may be included. Similarly, more than one item may be used herein in place of a single item. Where stated, a single item may be substituted for more than one of the items.

[0014] As used herein, the term "visible light transmittance" or "VLT" refers to the Transmitted through the light / transparent substrate system and visible to the human eye (i.e., 380 nm to 780 nm) The ratio of total light (having wavelengths between 100 and 200 nm) was measured using a BYK Haze Gard instrument. , can be measured according to TH ASTM C method.

[0015] As used herein, the term "haze value" refers to the haze value at 2.5° from the direction of the incident beam. The percentage of light transmitted through the composite film that is deflected beyond It can be measured according to TH ASTM C method using a ZeGard instrument.

[0016] As used herein, the term "reflectance" refers to a complex reflectance when illuminated by a light source. Indicates the measurement of visible light reflected from a film surface and uses a HunterLab instrument It can be measured according to ASTM E-1349 by

[0017] The embodiments described herein generally comprise a first transparent substrate and a first surface of the first transparent substrate. The composite film may include a first anti-reflective coating laminated to a surface of the first anti-reflective coating. The anti-reflective coating comprises a first UV-curable acrylate binder, a photoinitiator component, and a first The antireflective coating may include silica nanoparticles dispersed therein. The composite film formed in accordance with the present invention has a high VLT, a low haze value, a low reflectance or the like. The combination may have certain properties.

[0018] These concepts will be understood with reference to the embodiments described below, which are illustrative and not limiting of the scope of the present disclosure. and is better understood.

[0019] FIG. 1 is a cross-sectional view of a portion of an exemplary composite film 100 according to embodiments described herein. As shown in FIG. 1, the composite film 100 includes a first transparent substrate 110 and a second transparent substrate 112. A first anti-reflection coating 120 is deposited on the first surface 112 of the first transparent substrate 110. may include.

[0020] According to certain embodiments, the composite film 100 may have a particular VLT. For example, The composite film 100 has a porosity of at least about 93.2%, such as at least about 93.4% or less. At least about 93.6%, or at least about 93.8%, or at least about 94.0%, or less At least about 94.2%, or at least about 94.4%, or at least about 94.6%, or less At least about 94.8%, or at least about 95.0%, or at least about 95.2%, or at least or at least about 95.4%, or at least about 95.6%, or at least about 95.8%, or even less According to yet another embodiment, the composite film 10 may have a VLT of at least about 96.0%. 0 may have a VLT of about 99.9% or less. It is recognized that a patient may have a VLT within a range between and including any of the above values. The composite film 100 may have any of the values ​​between and including the minimum and maximum values ​​set forth above. It is further recognized that the VLT may have any value, including

[0021] According to yet other embodiments, the composite film 100 may have a particular haze value. For example, the composite film 100 has a thickness of about 3.0% or less, such as about 2.9% or less or about 2.8% or less. or about 2.7% or less, or about 2.6% or less, or about 2.5% or less, or about 2.4% or less, or about 2 0.3% or less, or about 2.2% or less, or about 2.1% or less, or about 2.0% or less, or about 1.9% or less or about 1.8% or less, or about 1.7% or less, or about 1.6% or less, or about 1.5% or less, or about The composite film 100 may have a haze value of about 1.4% or less, or even about 1.3% or less. It will be appreciated that the haze value may be within a range including any of the values ​​recited above. 00 may have any haze value between and including any of the above values. is further recognized.

[0022] According to other embodiments, the composite film 100 may have a particular reflectance. For example, The composite film 100 has a viscosity of about 7.0% or less, for example, about 6.9% or less or about 6.8% or less. is about 6.7% or less, or about 6.6% or less, or about 6.5% or less, or about 6.4% or less, or about 6. 3% or less, or about 6.2% or less, or about 6.1% or less, or about 6.0% or less, or about 5.9% or less or about 5.8% or less, or about 5.7% or less, or about 5.6% or less, or about 5.5% or less, or about 5 0.4% or less, or about 5.3% or less, or about 5.2% or less, or about 5.1% or less, or about 5.0% or less The composite film 100 may have a reflectance between and including the minimum and maximum values ​​set forth above. It will be appreciated that the composite film 10 may have a reflectance within a range including any of these values. 0 is any value of reflectance between and including the minimum and maximum values ​​listed above It is further recognized that the

[0023] According to yet another embodiment, the first anti-reflective coating 120 has a particular thickness. For example, the first anti-reflective coating 120 may be at least about 50 nm thick, e.g. At least about 60 nm, or at least about 70 nm, or at least about 80 nm, or at least About 90 nm or at least about 100 nm or at least about 110 nm or at least about 12 0 nm or at least about 130 nm or at least about 140 nm or at least about 150 nm or at least about 160 nm or at least about 170 nm or at least about 180 nm 100 nm or at least about 190 nm or at least about 200 nm thick. According to an embodiment, the anti-reflective coating 120 has a thickness of about 500 nm or less, for example about 490 nm or less. nm or less, or about 480 nm or less, or about 470 nm or less, or about 460 nm or less, or about 450 nm or less, or about 440 nm or less, or about 430 nm or less, or about 420 nm or less, or about 410 nm or less, or about 400 nm or less, or about 390 nm or less, or about 380 nm or less, or about 370 nm or less, or about 360 nm or less, or about 350 nm or less, or about 340 nm or less, or about 330 nm or less, or about 320 nm or less, or about 310 nm or less, or even about 300 nm or less The first anti-reflective coating 120 may have a thickness between the minimum and maximum values. It will be appreciated that the first anti-reflective coating may have a thickness within a range including any of these values. The thermal barrier coating 120 may be any value between and including the minimum and maximum values ​​set forth above. It is further recognized that the thickness of the film may be any value, including, but not limited to, 0.1 mm to 1.5 mm.

[0024] According to yet another embodiment, the first anti-reflective coating 120 has a specific ratio AC1 SiO2 / AC1B AC1 SiO2 The first anti-reflective coating 120 The weight percentage of silica nanoparticles in the first antireflective coating 120 relative to the total weight of the The concentration in the AC1 B is the total weight of the first anti-reflective coating 120 The weight percent of the first UV-curable acrylate binder in the first antireflective coating 120 For example, the first antireflective coating 120 has a concentration of at least about 0.01, for example at least about 0.05 or at least about 0.07 or at least about 0. 1 or at least about 0.12 or at least about 0.15 or at least about 0.17 or less at least about 0.20 or at least about 0.22 or at least about 0.25 or at least A ratio AC1 of about 0.27 or even at least about 0.30 SiO2 / AC1 B may have: According to yet other embodiments, the first antireflective coating 120 has an IR ratio of about 1.3 or less, e.g. For example, about 1.2 or less, or about 1.1 or less, or about 1.0 or less, or about 0.9 or less, or about 0.8 or less, Ratio AC1 of about 0.7 or less, or about 0.6 or less, or even about 0.5 or less SiO2 / AC1 B The first anti-reflective coating 120 may have a refractive index between the minimum and maximum values ​​given above, and Ratio AC1 in the range including any of these values SiO2 / AC1 B It is recognized that The first anti-reflective coating 120 is between the above minimum and maximum values ​​and Any value ratio AC1 including any of the values ​​above SiO2 / AC1 B It can further be said that Be recognized.

[0025] According to yet another embodiment, the first anti-reflective coating 120 is a first UV curable According to yet another embodiment, the first anti-reflective coating may include an acrylate binder. The first UV-curable acrylate binder in the group 120 is, for example, SR351LV, SR35 5, SR399, tetrafunctional acrylate monomer, pentafunctional acrylate monomer, pen Taerythritol tritetraacrylate (PETIA), Ebecry 140, Eb It can be ecryl 180, a multifunctional oligomer or a UV resin.

[0026] According to yet another embodiment, the first anti-reflective coating 120 comprises a first For example, the first antireflective coating 12 may include a UV-curable acrylate binder. 0 is at least about 40% by weight, for example at least about 50% by weight, based on the total weight of the first antireflective coating. At least about 42% by weight, or at least about 44% by weight, or at least about 46% by weight, or less at least about 48% by weight, or at least about 50% by weight, or at least about 52% by weight, or At least about 54% by weight, or at least about 56% by weight, or at least about 58% by weight, or even less The composition may have a first UV-curable acrylate binder concentration of at least about 60% by weight. According to an embodiment, the first anti-reflective coating 120 is about 95% by weight or less, for example about 93% by weight or less, or about 90% by weight or less, based on the total weight of about 88% by weight or less, or about 85% by weight or less, or about 83% by weight or less, or about 80% by weight or less, About 78% by weight or less, or about 75% by weight or less, or about 73% by weight or less, or even about 70% by weight or less The first antireflective coating may have a first UV-curable acrylate binder concentration below. 120 is the first value within the range between and including the above minimum and maximum values. It is recognized that the first antireflective coating may have a UV curable acrylate binder concentration of 1000 to 2000 nm. Any value between and including the above minimum and maximum values ​​may be used for the shaping 120. It is further recognized that the first UV-curable acrylate binder concentration may have a value of

[0027] According to yet another embodiment, the first antireflective coating 120 includes a photoinitiator component. According to yet another embodiment, the photoinitiator composition in the first antireflective coating 120 may be Minutes: Omnirad 184, Omnirad 819, Omnirad 1173, It may be CPI 6976, other similar photoinitiators, or any combination of the above.

[0028] According to yet another embodiment, the first anti-reflective coating 120 has a particular concentration of optical aperture. For example, the first antireflective coating 120 may include an initiator component. At least about 2% by weight, for example at least about 2.2% by weight, based on the total weight of the coating. is at least about 2.5 wt.%, or at least about 2.7 wt.%, or at least about 3.0 wt.% % or at least about 3.2% by weight or at least about 3.5% by weight or at least about 3.7 % by weight or at least about 4.0% by weight or at least about 4.2% by weight or at least about 4 .5% by weight or at least about 4.7% by weight or at least about 5.0% by weight or at least It may have a photoinitiator component concentration of about 5.2% by weight or even at least about 5.5% by weight. According to another embodiment, the first anti-reflective coating 120 is a first anti-reflective coating. About 10% by weight or less, for example about 9.8% by weight or less, or about 9.5% by weight or less, based on the total weight of the ingredient. % or less by weight, or about 9.3% or less by weight, or about 9.0% or less by weight, or about 8.8% or less by weight, or about 8 0.5% by weight or less, or about 8.3% by weight or less, or about 8.0% by weight or less, or about 7.8% by weight or less or about 7.5% by weight or less, or about 7.3% by weight or less, or about 7.0% by weight or less, or about 6.8% by weight or less The first antireflective coating may have a photoinitiator component concentration of about 6.5% by weight or less or even about 6.5% by weight or less. The coating 120 may have a thickness between and including any of the minimum and maximum values ​​listed above. It is recognized that the first antireflective coating 1 may have a photoinitiator component concentration within a range. 20 may be any value between and including the minimum and maximum values ​​listed above. It is further recognized that the composition may have an initiator component concentration.

[0029] According to yet another embodiment, the first anti-reflective coating 120 is a silicon-based coating having a specific concentration. For example, the first antireflective coating 120 may include a first antireflective At least about 5% by weight, for example at least about 6% by weight, based on the total weight of the coating At least about 7% by weight, or at least about 8% by weight, or at least about 9% by weight, or or at least about 10% by weight, or at least about 11% by weight, or at least about 12% by weight, or at least About 13% by weight or at least about 14% by weight or at least about 15% by weight or at least about 16% by weight or at least about 17% by weight or at least about 18% by weight or at least about 1 9% by weight or at least about 20% by weight or at least about 21% by weight or at least about 22% by weight % by weight or at least about 23% by weight or at least about 24% by weight or even at least about According to another embodiment, the first anti-reflective coating may have a silica nanoparticle concentration of 25% by weight. The antireflective coating 120 is about 60% by weight or more based on the total weight of the first antireflective coating. For example, about 58% by weight or less, or about 55% by weight or less, or about 53% by weight or less, or about 50% by weight or less % or less by weight, or about 48% or less by weight, or about 45% or less by weight, or about 43% or less by weight, or about 40% or less by weight % or less, or about 38% or less, or about 35% or less, or about 33% or less, or even about 3 The first anti-reflective coating 120 may have a silica nanoparticle concentration of 0% or less by weight. Silica nanoparticles within a range between and including any of the minimum and maximum values ​​set forth above. It will be appreciated that the first anti-reflective coating 120 may have any of the above minimum and and a maximum silica nanoparticle concentration of any value between and including any of the values. It is further recognized that

[0030] According to yet another embodiment, the silica nanoparticles in the first antireflective coating 120 are According to another embodiment, the first anti-reflective coating may be a surface-treated silica nanoparticle. The silica nanoparticles in ring 120 may be generally solid, spherical silica nanoparticles.

[0031] According to yet another embodiment, the first anti-reflective coating 120 is a polysiloxane, It may be surface treated with an acrylate or a combination thereof.

[0032] According to another embodiment, the silica nanoparticles in the first antireflective coating 120 are For purposes of the embodiments described herein, the average particle size may be a specific average particle size (D50). The average particle size (D50) is measured according to ASTM E2490. The silica nanoparticles in the first antireflective coating 120 are at least about 1 nm, e.g. For example, at least about 2 nm, or at least about 3 nm, or at least about 4 nm, or at least about 5 nm or at least about 6 nm or at least about 7 nm or at least about 8 nm or less At least about 10 nm, or at least about 11 nm, or at least about 12 nm, or at least about 13 nm or at least about 14 nm or at least about 15 nm or at least about 16 nm or having an average particle size (D50) of at least about 17 nm or even at least about 18 nm According to another embodiment, the silica nanoparticles in the first anti-reflective coating 120 are , about 500 nm or less, for example, about 400 nm or less, or about 300 nm or less, or about 200 nm or less or about 100 nm or less, or about 95 nm or less, or about 90 nm or less, or about 85 nm or less, or About 80 nm or less, or about 75 nm or less, or about 65 nm or less, or about 60 nm or less, or about 55 nm or less m or less, or about 50 nm or less, or about 45 nm or less, or about 40 nm or less, or about 35 nm or less, The first antireflective layer may have an average particle size (D50) of about 30 nm or less, or about 25 nm or less. The silica nanoparticles in the coating 120 are between and within the above minimum and maximum values. It is recognized that the average particle size (D50) of the first reaction may be within a range including any of the values. The silica nanoparticles in the anti-reflection coating 120 are between and including the minimum and maximum values ​​set forth above. It will be further recognized that the particle size may have any value, including any of the above values. can be.

[0033] According to another embodiment, the first anti-reflective coating 120 further comprises a slip agent. According to yet another embodiment, the slip agent may be included in a coating composition for use in the wet coating industry. Any known slip agent may be used, such as Tego glide 410, Tegora d 2100, Tegorad 2300, Tegorad 2500, BYK306, BYK307 and any combination thereof.

[0034] According to yet another embodiment, the first anti-reflective coating 120 is a specific concentration of slits. For example, the first anti-reflective coating 120 may include a coating agent. At least about 0.01% by weight, or at least about 0.5% by weight, based on the total weight of the coating. The composition may further have a slip agent concentration of at least about 1.0% by weight. In other words, the first anti-reflective coating 120 has a total weight of and a slip agent concentration of about 5% by weight or less, or about 4.5% by weight or less, or about 4.0% by weight or less. The first anti-reflective coating 120 may have a value between the minimum and maximum values ​​given above, and It is recognized that the slip agent concentration may be within a range including any of these values. The anti-reflective coating 120 may have a reflectance between the minimum and maximum values ​​given above, and at any of the values ​​therebetween. It will be further recognized that the slip agent concentration may be any value, including deviations.

[0035] According to yet another embodiment, the first antireflective coating 120 further comprises a wetting agent. According to yet another embodiment, the wetting agent may be any of the agents used in the wet coating industry. known wetting agents such as BYK-377, BYK-UV 3500, Tego 270, Or any combination thereof.

[0036] According to yet another embodiment, the first anti-reflective coating 120 has a specific concentration of wetting For example, the first anti-reflective coating 120 may include a first anti-reflective coating At least about 0.01% by weight, or at least about 0.05% by weight, or According to yet another embodiment, the first The anti-reflective coating 120 has a weight of about 0.3 with respect to the total weight of the first anti-reflective coating. % by weight or less, or about 0.25% by weight or less, or even about 0.2% by weight or less of a wetting agent concentration The first anti-reflective coating 120 has a reflectance between the minimum and maximum values ​​and between them. It will be appreciated that the slip agent concentration may be within a range including any of these values. The anti-reflection coating 120 may be any value between and including the minimum and maximum values ​​listed above. It is further recognized that the wetting agent concentration may be any value, including

[0037] According to another embodiment, the first anti-reflective coating 120 is a surface energy controlled According to yet another embodiment, the surface energy modifier is a wet Any known surface energy modifier used in the coating industry, e.g., BYK- 315, BYK-300, BYK-310, BY-378 or any combination thereof. do.

[0038] According to yet another embodiment, the first anti-reflective coating 120 has a surface area of ​​a particular concentration. For example, the first anti-reflective coating 120 may include an energy adjustment agent. At least about 0.01% by weight based on the total weight of the anti-glare coating or at least about 0. The surface energy modifier may have a concentration of at least about 0.05% by weight or at least about 0.1% by weight. According to another embodiment, the first anti-reflective coating 120 is About 0.30% by weight or less, or about 0.25% by weight or less, or even about 0. The first antireflective coating 12 may have a surface energy modifier concentration of 2% by weight or less. 0 is the surface area between and including the minimum and maximum values ​​listed above. It will be appreciated that the first antireflective coating 120 may have an energy modifier concentration. , any value of surface energy between and including the above minimum and maximum values. It is further recognized that the composition may have an energy adjusting agent concentration.

[0039] According to yet another embodiment, the first anti-reflective coating 120 is a second UV-curable According to yet another embodiment, a second UV-curable acrylate binder may be included. Acrylate binders include SR351LV, SR355, SR399, and tetrafunctional acrylates. Monomer, Pentafunctional Acrylate Monomer, Pentaerythritol Tritetraacrylate PETIA, Ebecryl 140, Ebecryl 180, Multifunctional Oligomers or UV resin.

[0040] According to yet another embodiment, the first anti-reflective coating 120 is a second anti-reflective coating having a specific concentration. For example, the first antireflective coating 12 may include a UV-curable acrylate binder. 0 is at least about 5.0 wt. % or less based on the total weight of the first antireflective coating at least about 7% by weight, or at least about 10% by weight, or at least about 12% by weight, or at least about 15% by weight, or at least about 17% by weight, or at least about 20% by weight, or at least about 22% by weight or even at least about 25% by weight of a second UV-curable acrylate binder; According to yet another embodiment, the first anti-reflective coating 120 may have a first about 60% by weight or less, or about 58% by weight or less, based on the total weight of the antireflective coating of about 55% by weight or less, or about 53% by weight or less, or about 50% by weight or less, or about 48% by weight or less, about 45% by weight or less, or about 43% by weight or less, or about 40% by weight or less of a second UV-curable acrylic The first antireflective coating 120 may have a binder concentration of at least one of the above minimum values ​​and A second UV-curable acrylate within a range between and including any of the maximum values. It will be appreciated that the first anti-reflective coating 120 may have a binder concentration of 0.1 to 0.5% by weight. A second UV curability of any value between and including the minimum and maximum values. It is further recognized that the composition may have an acrylate binder concentration.

[0041] According to yet other embodiments, the first transparent substrate 110 may have a particular thickness. For example, , the first transparent substrate 110 may be at least about 5 mils, such as at least about 6 mils or less. At least about 7 mils, or at least about 8 mils, or at least about 9 mils, or even at least about 1 According to another embodiment, the first transparent substrate 110 may have a thickness of about 15.0 mils. mils or less, for example about 14 mils or less, or about 13 mils or less, or about 12 mils or less, or about 11 mils The thickness of the first transparent substrate 110 may be between the minimum and maximum values ​​described above. It will be appreciated that the thickness of the first transparent substrate 1 may be within a range including any of these values. 10 thickness is any value between and including the minimum and maximum values ​​above It is further recognized that it may be.

[0042] According to yet another embodiment, the first transparent substrate 110 is laminated together by an adhesive. For example, the first transparent substrate 110 may be a transparent film. At least two films laminated together or at least three films laminated together by adhesive At least four films or adhesives laminated together with At least five films laminated together by adhesive or at least five films laminated together by adhesive At least 6 films or at least 7 films or adhesives laminated together with At least eight films laminated together with an adhesive or laminated together with an adhesive At least 9 films or at least 10 films laminated together by adhesive At least 11 films or adhesives laminated together At least 12 films laminated together or at least 10 films laminated together by adhesive At least 13 films or at least 14 or even 15 films laminated together could be.

[0043] According to another embodiment, the first transparent substrate 110 is made of polyethylene terephthalate ( According to yet another embodiment, the first transparent substrate 110 may include a P According to another embodiment, the transparent substrate 110 may be an optically transparent ET film. According to another embodiment, the transparent substrate 110 may be an optically transparent material. According to another embodiment, the transparent substrate 110 may be a single layer of optically transparent PET film. According to another embodiment, the transparent substrate 110 may comprise an optically transparent PET film. , may consist of a single layer of optically clear PET film.

[0044] According to yet another embodiment, the PET film of the first transparent substrate 110 has a specific thickness. For example, the PET film of the first transparent substrate 110 may have a thickness of at least about 5 mils, e.g. For example, at least about 6 mils, or at least about 7 mils, or at least about 8 mils, or at least It may have a thickness of about 9 mils or even at least about 10 mils. The PET film of the first transparent substrate 110 is about 15 mils or less, for example about 14 mils or less. The first transparent substrate may have a thickness of about 13 mils or less, or about 12 mils or less, or about 11 mils or less. The thickness of the PET film of the substrate 110 is between the above minimum and maximum values ​​and between these values. It is recognized that the range may include any of the above. The thickness of the film may be any value between and including the minimum and maximum values ​​listed above. It is further recognized that it may be.

[0045] FIG. 2 is a cross-sectional view of a portion of another exemplary composite film 200 according to embodiments described herein. As shown in FIG. 2, the composite film 200 includes a first transparent substrate 210, A first anti-reflective coating 22 is deposited on a first surface 212 of a first transparent substrate 210. 0 and a second anti-reflective coating disposed on the second surface 214 of the first transparent substrate 210. The sensor 200 may include a sensor 230.

[0046] As shown in FIG. 2, the composite film 200 and all of the other components described herein may be used in conjunction with the composite film 200. All components have any of the characteristics described herein with respect to the corresponding components in FIG. In particular, the composite film 200, the transparent substrate 210, and the The properties of the first anti-reflective coating 220 are the same as those of the composite film 100 shown in FIG. , as described herein with respect to the transparent substrate 110 and the first anti-reflective coating 120. It may have any of the corresponding properties.

[0047] According to certain embodiments, the composite film 200 may have a particular VLT. For example, The composite film 200 has a porosity of at least about 93.2%, such as at least about 93.4% or less. At least about 93.6%, or at least about 93.8%, or at least about 94.0%, or less At least about 94.2%, or at least about 94.4%, or at least about 94.6%, or less At least about 94.8%, or at least about 95.0%, or at least about 95.2%, or at least or at least about 95.4%, or at least about 95.6%, or at least about 95.8%, or even less According to yet another embodiment, the composite film 20 may have a VLT of at least about 96.0%. 0 may have a VLT of about 99.9% or less. It is recognized that a patient may have a VLT within a range between and including any of the above values. The composite film 200 may have any of the values ​​between and including the minimum and maximum values ​​listed above. It is further recognized that the VLT may have any value including

[0048] According to yet other embodiments, the composite film 200 may have a particular haze value. For example, the composite film 200 has a thickness of about 3% or less, such as about 2.9% or less, or about 2.8% or less, About 2.7% or less, or about 2.6% or less, or about 2.5% or less, or about 2.4% or less, or about 2.3% or less % or less, or about 2.2% or less, or about 2.1% or less, or about 2.0% or less, or about 1.9% or less, is about 1.8% or less, or about 1.7% or less, or about 1.6% or less, or about 1.5% or less, or about 1. The composite film 200 may have a haze value of about 4% or less, or even about 1.3% or less. It will be appreciated that the composite film 200 may have a haze value within a range including any of the values. It is further contemplated that the VLT may have any value between and including any of the above values. Be recognized.

[0049] According to other embodiments, the composite film 200 may have a particular reflectance. For example, , the composite film 200 has a viscosity of about 7.0% or less, for example, about 6.9% or less or about 6.8% or less. is about 6.7% or less, or about 6.6% or less, or about 6.5% or less, or about 6.4% or less, or about 6. 3% or less, or about 6.2% or less, or about 6.1% or less, or about 6.0% or less, or about 5.9% or less or about 5.8% or less, or about 5.7% or less, or about 5.6% or less, or about 5.5% or less, or about 5 0.4% or less, or about 5.3% or less, or about 5.2% or less, or about 5.1% or less, or about 5.0% or less The composite film 200 may have a reflectance between and including the minimum and maximum values ​​listed above. It will be appreciated that the composite film 20 may have a reflectance within a range including any of these values. 0 is any value of reflectance between and including the minimum and maximum values ​​listed above It is further recognized that the

[0050] According to yet another embodiment, the second anti-reflective coating 230 has a particular thickness. For example, the second anti-reflective coating 230 may be at least about 50 nm thick, e.g. At least about 60 nm, or at least about 70 nm, or at least about 80 nm, or at least About 90 nm or at least about 100 nm or at least about 110 nm or at least about 12 0 nm or at least about 130 nm or at least about 140 nm or at least about 150 nm or at least about 160 nm or at least about 170 nm or at least about 180 nm The thickness of the thin film may be at least about 190 nm or at least about 200 nm. According to other embodiments, the anti-reflective coating 120 has a thickness of about 500 nm or less, such as about 490 nm or less, or about 480 nm or less, or about 470 nm or less, or about 460 nm or less, or about 450 nm or less, or about 440 nm or less, or about 430 nm or less, or about 420 nm or less, or about 410 nm or less, or about 400 nm or less, or about 390 nm or less, or about 380 nm or less, or 370 nm or less, or about 360 nm or less, or about 350 nm or less, or about 340 nm or less, or about 330 nm or less, or about 320 nm or less, or about 310 nm or less, or even about 300 nm or less The second anti-reflective coating 230 may have a thickness between the minimum and maximum values. It will be appreciated that the second layer may have a thickness within a range including any of these values. The anti-reflective coating 230 is between and at any of the minimum and maximum values ​​given above. It is further recognized that the thickness of the layer may be any value, including

[0051] According to yet another embodiment, the second anti-reflective coating 230 has a specific ratio AC2 S iO2 / AC2 B AC2 SiO2 is the second anti-reflective coating 230 Percentage by weight of silica nanoparticles in the second antireflective coating 230 relative to the total weight is the concentration at B is the total weight of the second antireflective coating 230, The weight percent of the first UV-curable acrylate binder in the second antireflective coating 230 For example, the second antireflective coating 230 has a concentration of at least about 0. 0.01, for example at least about 0.05 or at least about 0.07 or at least about 0.1 or at least about 0.12, or at least about 0.15, or at least about 0.17, or less at least about 0.20 or at least about 0.22 or at least about 0.25 or at least about A ratio AC2 of 0.27 or even at least about 0.30 SiO2 / AC2 B It may have. According to other embodiments, the second anti-reflective coating 230 has an IR ratio of about 1.3 or less, e.g. about 1.2 or less, or about 1.1 or less, or about 1.0 or less, or about 0.9 or less, or about 0.8 or less, or Ratio AC2 of about 0.7 or less, or about 0.6 or less, or even about 0.5 or less SiO2 / AC2 B of The second anti-reflective coating 230 may have a reflectance between the above minimum and maximum values ​​and Ratio AC2 in the range including any of these values SiO2 / AC2 B It is recognized that The second anti-reflective coating 230 is between the above minimum and maximum values ​​and between them. Any value ratio AC2 including any value of SiO2 / AC2 B It is further recognized that It is recognized.

[0052] According to yet another embodiment, the second anti-reflective coating 230 is a first UV curable According to yet another embodiment, the second anti-reflective coating may include an acrylate binder. The first UV-curable acrylate binder in group 230 is SR351LV, SR355, S R399, Tetrafunctional acrylate monomer, Pentafunctional acrylate monomer, Pentaerythritol Thuritol tritetraacrylate (PETIA), Ebecry 140, Ebecr It can be yl 180, a multifunctional oligomer or a UV resin.

[0053] According to yet another embodiment, the second anti-reflective coating 230 comprises a first anti-reflective coating having a particular concentration. For example, the second anti-reflective coating 23 may include a UV-curable acrylate binder. 0 is at least about 40% by weight, for example at least about 50% by weight, based on the total weight of the first antireflective coating. At least about 42% by weight, or at least about 44% by weight, or at least about 46% by weight, or less at least about 48% by weight, or at least about 50% by weight, or at least about 52% by weight, or At least about 54% by weight, or at least about 56% by weight, or at least about 58% by weight, or even less The composition may have a first UV-curable acrylate binder concentration of at least about 60% by weight. According to an embodiment, the second anti-reflective coating 230 is a first anti-reflective coating about 95% by weight or less, for example about 93% by weight or less, or about 90% by weight or less, based on the total weight of about 88% by weight or less, or about 85% by weight or less, or about 83% by weight or less, or about 80% by weight or less, About 78% by weight or less, or about 75% by weight or less, or about 73% by weight or less, or even about 70% by weight or less The second antireflective coating may have a first UV-curable acrylate binder concentration below. 230 is the first value within the range between and including the above minimum and maximum values. It is recognized that the second anti-reflective coating may have a UV curable acrylate binder concentration of 100% or more. Any value between and including the above minimum and maximum values ​​may be used for the shaping 230. It is further recognized that the first UV-curable acrylate binder concentration may have a value of

[0054] According to yet another embodiment, the second antireflective coating 230 includes a photoinitiator component. According to yet another embodiment, the photoinitiator composition in the second antireflective coating 230 may be Minutes: Omnirad 184, Omnirad 819, Omnirad 1173, It may be CPI 6976, other similar photoinitiators, or any combination of the above.

[0055] According to yet another embodiment, the second anti-reflective coating 230 has a specific concentration of optical aperture. For example, the second antireflective coating 230 may include an initiator component. At least about 2% by weight, for example at least about 2.2% by weight, based on the total weight of the coating. is at least about 2.5 wt.%, or at least about 2.7 wt.%, or at least about 3.0 wt.% % or at least about 3.2% by weight or at least about 3.5% by weight or at least about 3.7 % by weight or at least about 4.0% by weight or at least about 4.2% by weight or at least about 4 .5% by weight or at least about 4.7% by weight or at least about 5.0% by weight or at least It may have a photoinitiator component concentration of about 5.2% by weight or even at least about 5.5% by weight. According to another embodiment, the second anti-reflective coating 230 is a first anti-reflective coating. About 10% by weight or less, for example about 9.8% by weight or less, or about 9.5% by weight or less, based on the total weight of the ingredient. % or less by weight, or about 9.3% or less by weight, or about 9.0% or less by weight, or about 8.8% or less by weight, or about 8 0.5% by weight or less, or about 8.3% by weight or less, or about 8.0% by weight or less, or about 7.8% by weight or less or about 7.5% by weight or less, or about 7.3% by weight or less, or about 7.0% by weight or less, or about 6.8% by weight or less The second antireflective coating may have a photoinitiator component concentration of about 6.5% by weight or less. The coating 230 may have a thickness between and including any of the minimum and maximum values ​​listed above. It will be appreciated that the second antireflective coating may have a photoinitiator component concentration within a range. 30 may be any value between and including the minimum and maximum values ​​listed above. It is further recognized that the composition may have an initiator component concentration.

[0056] According to yet another embodiment, the second anti-reflective coating 230 is a silicon-based coating having a specific concentration. For example, the second antireflective coating 230 may include nanoparticles. At least about 5% by weight, for example at least about 6% by weight, based on the total weight of the coating At least about 7% by weight, or at least about 8% by weight, or at least about 9% by weight, or or at least about 10% by weight, or at least about 11% by weight, or at least about 12% by weight, or at least About 13% by weight or at least about 14% by weight or at least about 15% by weight or at least about 16% by weight or at least about 17% by weight or at least about 18% by weight or at least about 1 9% by weight or at least about 20% by weight or at least about 21% by weight or at least about 22% by weight % by weight or at least about 23% by weight or at least about 24% by weight or even at least about According to another embodiment, the second anti-reflective coating may have a silica nanoparticle concentration of 25% by weight. The antireflective coating 230 is about 60% by weight or more based on the total weight of the first antireflective coating. For example, about 58% by weight or less, or about 55% by weight or less, or about 53% by weight or less, or about 50% by weight or less % or less by weight, or about 48% or less by weight, or about 45% or less by weight, or about 43% or less by weight, or about 40% or less by weight % or less, or about 38% or less, or about 35% or less, or about 33% or less, or even about 3 The second anti-reflective coating 230 may have a silica nanoparticle concentration of 0% or less by weight. Silica nanoparticles within a range between and including any of the minimum and maximum values ​​set forth above. It will be appreciated that the second anti-reflective coating 230 may have any of the above minimum and and a maximum silica nanoparticle concentration of any value between and including any of the values. It is further recognized that

[0057] According to yet another embodiment, the silica nanoparticles in the second antireflective coating 230 are According to another embodiment, the second anti-reflective coating may be a surface-treated silica nanoparticle. The silica nanoparticles in ring 230 may be generally solid, spherical silica nanoparticles.

[0058] According to yet another embodiment, the second anti-reflective coating 230 is a polysiloxane, It may be surface treated with an acrylate or a combination thereof.

[0059] According to another embodiment, the silica nanoparticles in the second antireflective coating 230 are For purposes of the embodiments described herein, the average particle size may be a specific average particle size (D50). The average particle size (D50) is measured according to ASTM E2490. The silica nanoparticles in the second antireflective coating 230 are at least about 1 nm, e.g. For example, at least about 2 nm, or at least about 3 nm, or at least about 4 nm, or at least about 5 nm or at least about 6 nm or at least about 7 nm or at least about 8 nm or less At least about 10 nm, or at least about 11 nm, or at least about 12 nm, or at least about 13 nm or at least about 14 nm or at least about 15 nm or at least about 16 nm or having an average particle size (D50) of at least about 17 nm or even at least about 18 nm According to another embodiment, the silica nanoparticles in the second anti-reflective coating 230 are , about 500 nm or less, for example, about 400 nm or less, or about 300 nm or less, or about 200 nm or less or about 100 nm or less, or about 95 nm or less, or about 90 nm or less, or about 85 nm or less, or About 80 nm or less, or about 75 nm or less, or about 65 nm or less, or about 60 nm or less, or about 55 nm or less m or less, or about 50 nm or less, or about 45 nm or less, or about 40 nm or less, or about 35 nm or less, The second reaction may have an average particle size (D50) of about 30 nm or less, or even about 25 nm or less. The silica nanoparticles in the anti-reflection coating 230 are between and including the minimum and maximum values ​​set forth above. It will be appreciated that the average particle size (D50) may be within a range including any of these values. The silica nanoparticles in the anti-reflective coating 230 of the second embodiment are between the minimum and maximum values ​​described above. and any value of the average particle size (D50) including any of these values. Be recognized.

[0060] According to yet another embodiment, the second anti-reflective coating 230 further comprises a slip agent. According to yet another embodiment, the slip agent may further comprise a tertiary ingredient in the wet coating industry. Any known slip agent may be used, such as Tego glide 410, Tegor ad 2100, Tegorad 2300, Tegorad 2500, BYK306 , BYK307 and any combination thereof.

[0061] According to yet another embodiment, the second anti-reflective coating 230 is a specific concentration of slits. For example, the second anti-reflective coating 230 may include a coating agent similar to that of the first anti-reflective coating. At least about 0.01% by weight, or at least about 0.5% by weight, based on the total weight of the coating. The composition may further have a slip agent concentration of at least about 1.0% by weight. In other words, the second anti-reflective coating 230 has a weight of about 100% relative to the total weight of the first anti-reflective coating. and a slip agent concentration of about 5% by weight or less, or about 4.5% by weight or less, or about 4.0% by weight or less. The second anti-reflective coating 230 may have a reflectance between the above minimum and maximum values ​​and It will be appreciated that the slip agent concentration may be within a range including any of these values. The anti-reflective coating 230 is between and at any of the minimum and maximum values ​​given above. It is further recognized that the slip agent concentration may be any value, including

[0062] According to yet another embodiment, the second anti-reflective coating 230 further comprises a wetting agent. According to yet another embodiment, the wetting agent may be any of the agents used in the wet coating industry. known wetting agents such as BYK-377, BYK-UV 3500, Tego 270, Or any combination thereof.

[0063] According to yet another embodiment, the second anti-reflective coating 230 has a specific concentration of wetting For example, the second anti-reflective coating 230 may include a At least about 0.01% by weight, or at least about 0.05% by weight, or According to yet another embodiment, the second The anti-reflective coating 230 has a weight of about 0.3 with respect to the total weight of the first anti-reflective coating. % by weight or less, or about 0.25% by weight or less, or even about 0.2% by weight or less of a wetting agent concentration The second anti-reflective coating 230 has a reflectance between the above minimum and maximum values ​​and between them. It is recognized that the slip agent concentration may be within a range including any of the values ​​of The protective coating 230 may be any of the values ​​between the minimum and maximum values ​​listed above. It will be further appreciated that the wetting agent concentration may have any value, including

[0064] According to another embodiment, the second anti-reflective coating 230 is a surface energy controlled According to yet another embodiment, the surface energy modifier is a wet Any known surface energy modifier used in the coating industry, e.g., BYK- 315, BYK-300, BYK-310, BY-378 or any combination thereof. do.

[0065] According to yet another embodiment, the second anti-reflective coating 230 has a surface area of ​​a particular concentration. For example, the second anti-reflective coating 230 may include an energy adjustment agent. At least about 0.01% by weight based on the total weight of the anti-glare coating or at least about 0. The surface energy modifier may have a concentration of at least about 0.05% by weight or at least about 0.1% by weight. According to another embodiment, the second anti-reflective coating 230 is a first anti-reflective coating. About 0.30% by weight or less, or about 0.25% by weight or less, or even about 0. The second antireflective coating 23 may have a surface energy modifier concentration of 2% by weight or less. Surface energy 0 in the range between and including the above minimum and maximum values It will be appreciated that the second anti-reflective coating 230 may have a concentration of an energy modifier. Any value of surface energy between and including the minimum and maximum values ​​listed above. It is further recognized that the composition may have a modifier concentration.

[0066] According to yet another embodiment, the second anti-reflective coating 230 is a second UV curable According to yet another embodiment, a second UV-curable acrylate binder may be included. Acrylate binders include SR351LV, SR355, SR399, and tetrafunctional acrylates. Monomer, Pentafunctional Acrylate Monomer, Pentaerythritol Tritetraacrylate PETIA, Ebecryl 140, Ebecryl 180, Multifunctional Oligomers or UV resin.

[0067] According to yet another embodiment, the second anti-reflective coating 230 comprises a second For example, the second anti-reflective coating 23 may include a UV-curable acrylate binder. 0 is at least about 5.0 wt. % or less based on the total weight of the first antireflective coating at least about 7% by weight, or at least about 10% by weight, or at least about 12% by weight, or at least about 15% by weight, or at least about 17% by weight, or at least about 20% by weight, or at least about 22% by weight or even at least about 25% by weight of a second UV-curable acrylate binder; According to yet another embodiment, the second anti-reflective coating 230 may have a first about 60% by weight or less, or about 58% by weight or less, based on the total weight of the antireflective coating of about 55% by weight or less, or about 53% by weight or less, or about 50% by weight or less, or about 48% by weight or less, about 45% by weight or less, or about 43% by weight or less, or about 40% by weight or less of a second UV-curable acrylic The second antireflective coating 230 may have a binder concentration of at least one of the minimum and maximum values ​​set forth above. The second UV-curable acrylate copolymer may be used in a range between and including any of the above values. It will be appreciated that the second antireflective coating 230 may have a combined concentration of at least one of the above minimums. The second UV-curable activator may have any value between and including the values ​​and the maximum value. It is further recognized that the binder may have a regulated binder concentration.

[0068] FIG. 3 is a cross-sectional view of a portion of another exemplary composite film 300 according to embodiments described herein. As shown in FIG. 3, the composite film 300 includes a first transparent substrate 310, A first anti-reflective coating 32 is deposited on a first surface 312 of a first transparent substrate 310. 0, a second anti-reflective coating deposited on the second surface 314 of the first transparent substrate 310; 330 and a first adhesive layer laminated to the surface 322 of the first anti-reflective coating 320. 340.

[0069] As shown in FIG. 3, the composite film 300 and all of the other components described herein may be used in conjunction with the composite film 300. All components have any of the characteristics described herein with respect to the corresponding components in FIGS. In particular, the composite film 300 and the transparent substrate 3 shown in FIG. 10. Characteristics of the first anti-reflective coating 320 and the second anti-reflective coating 330 2 (FIG. 1), a composite film 200 (100), a transparent substrate 210 (11 0), the first anti-reflective coating 220 (120) and the second anti-reflective coating 2 30. It may have any of the corresponding characteristics described herein with respect to 30.

[0070] According to certain embodiments, the composite film 300 may have a particular VLT. For example, The composite film 300 has a porosity of at least about 93.2%, such as at least about 93.4% or less. At least about 93.6%, or at least about 93.8%, or at least about 94.0%, or less At least about 94.2%, or at least about 94.4%, or at least about 94.6%, or less At least about 94.8%, or at least about 95.0%, or at least about 95.2%, or at least or at least about 95.4%, or at least about 95.6%, or at least about 95.8%, or even less According to yet another embodiment, the composite film 30 may have a VLT of at least about 96.0%. 0 may have a VLT of about 99.9% or less. It is recognized that a patient may have a VLT within a range between and including any of the above values. The composite film 300 may have any of the values ​​between the minimum and maximum values ​​listed above. It is further recognized that the VLT may have any value including

[0071] According to yet other embodiments, the composite film 300 may have a particular haze value. For example, the composite film 300 has a thickness of about 3% or less, such as about 2.9% or less, or about 2.8% or less, About 2.7% or less, or about 2.6% or less, or about 2.5% or less, or about 2.4% or less, or about 2.3% or less % or less, or about 2.2% or less, or about 2.1% or less, or about 2.0% or less, or about 1.9% or less, is about 1.8% or less, or about 1.7% or less, or about 1.6% or less, or about 1.5% or less, or about 1. The composite film 300 may have a haze value of 4% or less, or even about 1.3% or less. It will be appreciated that the composite film 300 may have a haze value within a range including any of the values. has a VLT of any value between and including any of the above values. It is further recognized that

[0072] According to other embodiments, the composite film 300 may have a particular reflectance. For example, The composite film 300 has a thickness of about 7.0% or less, for example, about 6.9% or less or about 6.8% or less. is about 6.7% or less, or about 6.6% or less, or about 6.5% or less, or about 6.4% or less, or about 6. 3% or less, or about 6.2% or less, or about 6.1% or less, or about 6.0% or less, or about 5.9% or less or about 5.8% or less, or about 5.7% or less, or about 5.6% or less, or about 5.5% or less, or about 5 0.4% or less, or about 5.3% or less, or about 5.2% or less, or about 5.1% or less, or about 5.0% or less The composite film 300 may have a reflectance between and including the minimum and maximum values ​​listed above. It will be appreciated that the composite film 30 may have a reflectance within a range including any of these values. 0 is any value of reflectance between and including the minimum and maximum values ​​listed above It is further recognized that the

[0073] According to yet another embodiment, the first adhesive layer 340 is made of any suitable adhesive material for use in the adhesives industry. Any known pressure sensitive adhesive, such as Aroset 1452, Aroset 1452 manufactured by Ashland, et 1450, Aroset 6428, Duro-Tak 222A, Duro-T ak 80-1093 or combinations thereof.

[0074] According to still other embodiments, the first adhesive layer 340 may have a particular thickness. For example, , the first adhesive layer 340 may be at least about 2 μm, such as at least about 5 μm or less. At least about 7 μm, or at least about 10 μm, or at least about 12 μm, or at least 15 μm 10 μm or at least about 17 μm or even at least about 20 μm. According to this embodiment, the first adhesive layer 340 has a thickness of about 50 μm or less, for example about 48 μm or less. or about 45 μm or less, or about 43 μm or less, or about 40 μm or less, or about 38 μm or less, or about 3 It may have a thickness of 5 μm or less, or about 33 μm or less, or even about 30 μm or less. The adhesive layer 340 has a range between and including any of the minimum and maximum values ​​set forth above. It will be appreciated that the first adhesive layer 340 may have a thickness between the minimum and maximum values ​​set forth above. It is further recognized that the thickness of the slit may be any value including, but not limited to, any of the values. .

[0075] According to yet other embodiments, the first adhesive layer 340 may include nanoparticles. According to an embodiment, the nanoparticles in the first adhesive layer 340 are surface treated silica nanoparticles. According to another embodiment, silica nanoparticles in the second anti-reflective coating 340 may be can be generally solid, spherical silica nanoparticles.

[0076] According to yet another embodiment, the nanoparticles in the first adhesive layer 340 have a particular average particle size ( For purposes of the embodiments described herein, the average particle size (D50) may be , measured according to ASTM E2490. According to an embodiment, the first adhesive layer 3 The nanoparticles in 40 are at least about 1 μm, for example at least about 2 μm or at least about 3 μm or at least about 4 μm or at least about 5 μm or at least about 6 μm or less At least about 7 μm, or at least about 8 μm, or at least about 10 μm, or at least about 11 μm or at least about 12 μm or at least about 13 μm or at least about 14 μm or At least about 15 μm, or at least about 16 μm, or at least about 17 μm, or even less According to another embodiment, the first contact may have an average particle size (D50) of at least about 18 μm. The nanoparticles in the adhesive layer 340 are about 500 μm or less, for example about 400 μm or less or about 300 μm or less. μm or less, or about 200 μm or less, or about 100 μm or less, or about 95 μm or less, or about 90 μm or less than about 85 μm or less than about 80 μm or less than about 75 μm or less than about 65 μm or about 60 μm or less, or about 55 μm or less, or about 50 μm or less, or about 45 μm or less, or About 40 μm or less, or about 35 μm or less, or about 30 μm or less, or even about 25 μm or less The nanoparticles in the first adhesive layer 340 may have an average particle size (D50) of the above minimum value or less. The particles may have an average particle size (D50) within a range between and including any of the maximum and minimum values. It will be appreciated that the nanoparticles in the first adhesive layer 340 may be between the minimum and maximum values ​​set forth above. It is further understood that the particles may have an average particle size (D50) of any value between 0.1 and 0.5 mm, and any value therebetween. It is recognized by others.

[0077] FIG. 4 is a cross-sectional view of a portion of another exemplary composite film 400 according to embodiments described herein. As shown in FIG. 4, the composite film 400 includes a first transparent substrate 410, A first anti-reflective coating 42 is deposited on a first surface 412 of a first transparent substrate 410. 0, a second anti-reflective coating deposited on the second surface 414 of the first transparent substrate 410. 430, a first adhesive layer 430 laminated to the surface 422 of the first anti-reflective coating 420 40 and a second transparent substrate 450 laminated to the first adhesive layer 440.

[0078] As shown in FIG. 4, a composite film 400 and all of the following description of the composite film 400 are provided. All components have the characteristics described herein with respect to the corresponding components in FIGS. In particular, the composite film 400 shown in FIG. A plate 410, a first anti-reflective coating 420, a second anti-reflective coating 430, and The properties of the first adhesive layer 440 are the same as those of the composite film 300 shown in FIG. (200, 100), transparent substrate 310 (210, 110), first anti-reflection coating 320 (220, 120), the second anti-reflective coating 330 (230) and the first contact It may have any of the corresponding characteristics described herein with respect to adhesive layer 340.

[0079] According to certain embodiments, the composite film 400 may have a particular VLT. For example, The composite film 400 has a porosity of at least about 93.2%, such as at least about 93.4% or less. At least about 93.6%, or at least about 93.8%, or at least about 94.0%, or less At least about 94.2%, or at least about 94.4%, or at least about 94.6%, or less At least about 94.8%, or at least about 95.0%, or at least about 95.2%, or at least or at least about 95.4%, or at least about 95.6%, or at least about 95.8%, or even less According to yet another embodiment, the composite film 40 may have a VLT of at least about 96.0%. 0 may have a VLT of about 99.9% or less. It is recognized that a patient may have a VLT within a range between and including any of the above values. The composite film 400 may have any of the values ​​between and including the minimum and maximum values ​​set forth above. It is further recognized that the VLT may have any value including

[0080] According to yet other embodiments, the composite film 400 can have a particular haze value. For example, the composite film 400 has a thickness of about 3% or less, such as about 2.9% or less, or about 2.8% or less, About 2.7% or less, or about 2.6% or less, or about 2.5% or less, or about 2.4% or less, or about 2.3% or less % or less, or about 2.2% or less, or about 2.1% or less, or about 2.0% or less, or about 1.9% or less, is about 1.8% or less, or about 1.7% or less, or about 1.6% or less, or about 1.5% or less, or about 1. The composite film 400 may have a haze value of 4% or less, or even about 1.3% or less. It will be appreciated that the composite film 400 may have a haze value within a range including any of the values. It is further contemplated that the VLT may have any value between and including any of the above values. Be recognized.

[0081] According to other embodiments, the composite film 400 may have a particular reflectance. For example, , the composite film 400 has a thickness of about 7.0% or less, for example, about 6.9% or less or about 6.8% or less. is about 6.7% or less, or about 6.6% or less, or about 6.5% or less, or about 6.4% or less, or about 6. 3% or less, or about 6.2% or less, or about 6.1% or less, or about 6.0% or less, or about 5.9% or less or about 5.8% or less, or about 5.7% or less, or about 5.6% or less, or about 5.5% or less, or about 5 0.4% or less, or about 5.3% or less, or about 5.2% or less, or about 5.1% or less, or about 5.0% or less The composite film 400 may have a reflectance between and including the minimum and maximum values ​​listed above. It will be appreciated that the composite film 40 may have a reflectance within a range including any of these values. 0 is any value of reflectance between and including the minimum and maximum values ​​listed above It is further recognized that the

[0082] According to yet other embodiments, the second transparent substrate 450 may have a particular thickness. For example, , the second transparent substrate 450 may be at least about 5 mils, such as at least about 6 mils or less. At least about 7 mils, or at least about 8 mils, or at least about 9 mils, or even at least about 1 According to another embodiment, the second transparent substrate 450 may have a thickness of about 15.0 mils. mils or less, for example about 14 mils or less, or about 13 mils or less, or about 12 mils or less, or about 11 mils The thickness of the second transparent substrate 450 may be between the minimum and maximum values ​​described above. It will be appreciated that the thickness of the second transparent substrate 4 may be within a range including any of these values. 50 thickness is any value between and including the minimum and maximum values ​​listed above. It is further recognized that it may be.

[0083] According to another embodiment, the second transparent substrate 450 may include a PET film. According to another embodiment, the second transparent substrate 450 may be made of a PET film. According to an embodiment, the transparent substrate 110 may include an optically transparent PET film. According to another embodiment, the transparent substrate 110 may be made of an optically clear PET film. According to another embodiment, the transparent substrate 110 comprises a single layer of optically clear PET film. According to another embodiment, the transparent substrate 110 is a single layer optically clear PET film. The film may consist of:

[0084] According to yet another embodiment, the PET film of the second transparent substrate 450 has a specific thickness. For example, the PET film of the second transparent substrate 450 may have a thickness of at least about 5 mils, e.g. For example, at least about 6 mils, or at least about 7 mils, or at least about 8 mils, or at least It may have a thickness of about 9 mils or even at least about 10 mils. The PET film of the second transparent substrate 450 is about 15 mils or less, for example about 14 mils or less. The second transparent layer may have a thickness of about 13 mils or less, or about 12 mils or less, or about 11 mils or less. The thickness of the PET film of the substrate 450 is between the above minimum and maximum values ​​and between those values. It is recognized that the range may include any of the above. The thickness of the film may be any value between and including the minimum and maximum values ​​listed above. It is further recognized that it may be.

[0085] FIG. 5a illustrates a portion of another exemplary composite film 500 according to embodiments described herein. As shown in FIG. 5a, the composite film 500 includes a first transparent substrate 51. 0. A first anti-reflective coating deposited on the first surface 512 of the first transparent substrate 510. 520, a second anti-reflective coating deposited on the second surface 514 of the first transparent substrate 510. 530, a first adhesive layer laminated to the surface 522 of the first anti-reflective coating 520. layer 540, a second transparent substrate 550 laminated to the first adhesive layer 540, and a second transparent substrate 5 A second adhesive layer 560 is laminated to the surface 552 of the substrate 50 and a second adhesive layer 560 is laminated to the second adhesive layer 560. The transparent substrate 570 may include a third transparent substrate 570 disposed therebetween.

[0086] 5a and all of the other components described with respect to the composite film 500. The components have the characteristics described herein with respect to the corresponding components in FIGS. In particular, the composite film 500 shown in FIG. A substrate 510, a first anti-reflective coating 520, a second anti-reflective coating 530, The characteristics of the first adhesive layer 540 and the second transparent substrate 550 are shown in FIG. As shown in FIG. 1, a composite film 400 (300, 200, 100), a transparent substrate 410 (310 , 210, 110), a first anti-reflective coating 420 (320, 220, 120), The second anti-reflective coating 430 (330, 230), the first adhesive layer 440 (340 ) and any of the corresponding characteristics described herein with respect to second transparent substrate 450. possible.

[0087] According to certain embodiments, the composite film 500 may have a particular VLT. For example, The composite film 500 has a porosity of at least about 93.2%, such as at least about 93.4% or less. At least about 93.6%, or at least about 93.8%, or at least about 94.0%, or less At least about 94.2%, or at least about 94.4%, or at least about 94.6%, or less At least about 94.8%, or at least about 95.0%, or at least about 95.2%, or at least or at least about 95.4%, or at least about 95.6%, or at least about 95.8%, or even less According to yet another embodiment, the composite film 50 may have a VLT of at least about 96.0%. 0 may have a VLT of about 99.9% or less. It is recognized that a patient may have a VLT within a range between and including any of the above values. The composite film 500 may have any of the values ​​between and including the minimum and maximum values ​​set forth above. It is further recognized that the VLT may have any value including

[0088] According to yet other embodiments, the composite film 500 can have a particular haze value. For example, the composite film 500 has a film thickness of about 3% or less, such as about 2.9% or less, or about 2.8% or less, About 2.7% or less, or about 2.6% or less, or about 2.5% or less, or about 2.4% or less, or about 2.3% or less % or less, or about 2.2% or less, or about 2.1% or less, or about 2.0% or less, or about 1.9% or less, is about 1.8% or less, or about 1.7% or less, or about 1.6% or less, or about 1.5% or less, or about 1. The composite film 500 may have a haze value of 4% or less, or even about 1.3% or less. It will be appreciated that the composite film 500 may have a haze value within a range including any of the values. It is further preferred that the haze value of the coating composition has a value between and including any of the above values. is recognized.

[0089] According to other embodiments, the composite film 500 may have a particular reflectance. For example, The composite film 500 has a viscosity of about 7.0% or less, for example, about 6.9% or less or about 6.8% or less. is about 6.7% or less, or about 6.6% or less, or about 6.5% or less, or about 6.4% or less, or about 6. 3% or less, or about 6.2% or less, or about 6.1% or less, or about 6.0% or less, or about 5.9% or less or about 5.8% or less, or about 5.7% or less, or about 5.6% or less, or about 5.5% or less, or about 5 0.4% or less, or about 5.3% or less, or about 5.2% or less, or about 5.1% or less, or about 5.0% or less The composite film 500 may have a reflectance between and including the minimum and maximum values ​​listed above. It will be appreciated that the composite film 50 may have a reflectance within a range including any of these values. 0 is any value of reflectance between and including the minimum and maximum values ​​listed above It is further recognized that the

[0090] According to yet another embodiment, the second adhesive layer 560 is made of any suitable adhesive material for use in the adhesives industry. Any known pressure sensitive adhesive, such as Aroset 1452, Aroset 1452 manufactured by Ashland, et 1450, Aroset 6428, Duro-Tak 222A, Duro-T ak 80-1093 or combinations thereof.

[0091] According to still other embodiments, the second adhesive layer 560 can have a particular thickness. For example, , the second adhesive layer 560 may be at least about 2 μm, such as at least about 5 μm or less. At least about 7 μm, or at least about 10 μm, or at least about 12 μm, or at least 15 μm 10 μm or at least about 17 μm or even at least about 20 μm. According to this embodiment, the second adhesive layer 560 has a thickness of about 50 μm or less, for example about 48 μm or less. or about 45 μm or less, or about 43 μm or less, or about 40 μm or less, or about 38 μm or less, or about 3 The second adhesive may have a thickness of 5 μm or less, or about 33 μm or less, or even about 30 μm or less. The adhesive layer 560 has a range between and including any of the minimum and maximum values ​​set forth above. It will be appreciated that the second adhesive layer 560 may have a thickness between the minimum and maximum values ​​set forth above. It is further recognized that the thickness of the slit may be any value including, but not limited to, any of the values. .

[0092] According to yet other embodiments, the second adhesive layer 560 may include nanoparticles. According to an embodiment, the nanoparticles in the second adhesive layer 560 are surface treated silica nanoparticles. According to another embodiment, silica nanoparticles in the second anti-reflective coating 560 may be used. can be generally solid, spherical silica nanoparticles.

[0093] According to yet another embodiment, the nanoparticles in the second adhesive layer 560 have a particular average particle size ( For purposes of the embodiments described herein, the average particle size (D50) may be , measured according to ASTM E2490. According to an embodiment, the second adhesive layer 5 The nanoparticles in 60 are at least about 1 nm, for example at least about 2 nm or at least about 3 nm or at least about 4 nm or at least about 5 nm or at least about 6 nm or less At least about 7 nm, or at least about 8 nm, or at least about 10 nm, or at least about 11 nm or at least about 12 nm or at least about 13 nm or at least about 14 nm or At least about 15 nm, or at least about 16 nm, or at least about 17 nm, or even less According to another embodiment, the second contact may have an average particle size (D50) of at least about 18 nm. The nanoparticles in the adhesive layer 560 are about 500 nm or less, for example about 400 nm or less or about 300 nm or less. nm or less, or about 200 nm or less, or about 100 nm or less, or about 95 nm or less, or about 90 nm or less than about 85 nm or less than about 80 nm or less than about 75 nm or less than about 65 nm or less About 60 nm or less, or about 55 nm or less, or about 50 nm or less, or about 45 nm or less, or about 40 nm or less Average particle size (D50) of about 35 nm or less, about 30 nm or less, or about 25 nm or less The nanoparticles in the second adhesive layer 560 may have a density between the minimum and maximum values ​​given above, and It will be appreciated that the average particle size (D50) may fall within a range including any of these values. The nanoparticles in the second adhesive layer 560 are between and within the above minimum and maximum values. It will be further recognized that the particles may have an average particle size (D50) of any value including any of the above.

[0094] According to yet other embodiments, the third transparent substrate 570 may have a particular thickness. For example, , the third transparent substrate 570 may be at least about 5 mils, such as at least about 6 mils or less. At least about 7 mils, or at least about 8 mils, or at least about 9 mils, or even at least about 1 According to another embodiment, the third transparent substrate 570 may have a thickness of about 15.0 mils. mils or less, for example about 14 mils or less, or about 13 mils or less, or about 12 mils or less, or about 11 mils The thickness of the third transparent substrate 570 may be between the above minimum and maximum values. It will be appreciated that the thickness of the third transparent substrate 5 may be within a range including any of these values. 70 thickness is any value between and including the minimum and maximum values ​​listed above. It is further recognized that it may be.

[0095] According to another embodiment, the third transparent substrate 570 may include a PET film. According to another embodiment, the third transparent substrate 570 may be made of a PET film. According to an embodiment, the transparent substrate 110 may include an optically transparent PET film. According to another embodiment, the transparent substrate 110 may be made of an optically clear PET film. According to another embodiment, the transparent substrate 110 comprises a single layer of optically clear PET film. According to another embodiment, the transparent substrate 110 is a single layer optically clear PET film. The film may consist of:

[0096] According to yet another embodiment, the PET film of the third transparent substrate 570 has a specific thickness. For example, the PET film of the third transparent substrate 570 may have a thickness of at least about 5 mils, e.g. For example, at least about 6 mils, or at least about 7 mils, or at least about 8 mils, or at least It may have a thickness of about 9 mils or even at least about 10 mils. The PET film of the third transparent substrate 570 is about 15 mils or less, for example about 14 mils or less. The third transparent layer may have a thickness of about 13 mils or less, or about 12 mils or less, or about 11 mils or less. The thickness of the PET film of the substrate 570 is between the above minimum and maximum values ​​and between those values. It is recognized that the range may include any of the above. The thickness of the film may be any value between and including the minimum and maximum values ​​listed above. It is further recognized that it may be.

[0097] FIG. 5b illustrates a portion of another exemplary composite film 501 according to embodiments described herein. As shown in FIG. 5a, the composite film 500 includes a first transparent substrate 51. 0. A first anti-reflective coating deposited on the first surface 512 of the first transparent substrate 510. 520, a second anti-reflective coating deposited on the second surface 514 of the first transparent substrate 510. 530, a first adhesive layer laminated to the surface 522 of the first anti-reflective coating 520. layer 540, a second transparent substrate 550 laminated to the first adhesive layer 540, and a second adhesive layer Four repeating top transparent substrate configurations each including a third transparent substrate 570 laminated to 560. It may include element 590.

[0098] The number of repeating upper transparent substrate elements 590 shown in FIG. 5b is exemplary and not limiting. It will be appreciated that, according to certain embodiments, multiple The composite film 501 has a certain number of repeating top layer components, for example at least three repeating top layers. A transparent substrate element 590 or at least four repeating upper transparent substrate elements 590 or at least At least five repeating upper transparent substrate components 590 or at least six repeating upper transparent substrate structures A repeating upper transparent substrate component 590 or at least 7 repeating upper transparent substrate components 590 or at least 8 or at least nine repeating upper transparent substrate elements 59 It may include 0 or at least 10 repeating top transparent substrate elements 590.

[0099] According to certain embodiments, the composite film 501 may have a particular VLT. For example, The composite film 501 has a porosity of at least about 93.2%, such as at least about 93.4% or less. At least about 93.6%, or at least about 93.8%, or at least about 94.0%, or less At least about 94.2%, or at least about 94.4%, or at least about 94.6%, or less At least about 94.8%, or at least about 95.0%, or at least about 95.2%, or at least or at least about 95.4%, or at least about 95.6%, or at least about 95.8%, or even less According to yet another embodiment, the composite film 50 may have a VLT of at least about 96.0%. 1 may have a VLT of about 99.9% or less. It is recognized that a patient may have a VLT within a range between and including any of the above values. The composite film 501 may have any of the values ​​between the minimum and maximum values ​​listed above. It is further recognized that the VLT may have any value including

[0100] According to yet other embodiments, the composite film 501 can have a particular haze value. For example, the composite film 501 has a film thickness of about 3% or less, such as about 2.9% or less or about 2.8% or less. About 2.7% or less, or about 2.6% or less, or about 2.5% or less, or about 2.4% or less, or about 2.3% or less % or less, or about 2.2% or less, or about 2.1% or less, or about 2.0% or less, or about 1.9% or less, is about 1.8% or less, or about 1.7% or less, or about 1.6% or less, or about 1.5% or less, or about 1. The composite film 501 may have a haze value of 4% or less, or even about 1.3% or less. It will be appreciated that the composite film 501 may have a haze value within a range including any of the values. It is further understood that the haze value may be any value between and including any of the above values. It is recognized by others.

[0101] According to other embodiments, the composite film 501 may have a particular reflectance. For example, , the composite film 501 has a viscosity of about 7.0% or less, for example, about 6.9% or less or about 6.8% or less. is about 6.7% or less, or about 6.6% or less, or about 6.5% or less, or about 6.4% or less, or about 6. 3% or less, or about 6.2% or less, or about 6.1% or less, or about 6.0% or less, or about 5.9% or less or about 5.8% or less, or about 5.7% or less, or about 5.6% or less, or about 5.5% or less, or about 5 0.4% or less, or about 5.3% or less, or about 5.2% or less, or about 5.1% or less, or about 5.0% or less The composite film 501 may have a reflectance between and including the minimum and maximum values ​​listed above. It will be appreciated that the composite film 50 may have a reflectance within a range including any of these values. Any value of reflectance between and including the minimum and maximum values ​​listed above. It is further recognized that the

[0102] FIG. 6a illustrates a portion of another exemplary composite film 600 according to embodiments described herein. As shown in FIG. 6a, the composite film 600 includes a first transparent substrate 61. 0, a first anti-reflective coating deposited on a first surface 612 of a first transparent substrate 610; 620, a second anti-reflective coating deposited on the second surface 614 of the first transparent substrate 610. 630, a first adhesive layer laminated to the surface 622 of the first anti-reflective coating 620. layer 640, a second transparent substrate 650 laminated to the first adhesive layer 640, and a second transparent substrate It may include a third anti-reflective coating 680 deposited on surface 652 of 650 .

[0103] 6a and all of the other components described with respect to the composite film 600. The components are as described herein with reference to the corresponding components in Figures 1, 2, 3, 4, 5a and 5b. It will be appreciated that the composite film may have any of the properties described above. In particular, the composite film shown in FIG. 600, a transparent substrate 610, a first anti-reflective coating 620, a second anti-reflective coating The properties of the casing 630, the first adhesive layer 640 and the second transparent substrate 650 are shown in FIG. or composite film 500 (400, 300, 20 0, 100), transparent substrate 510 (410, 310, 210, 110), first anti-reflection coating coating 520 (420, 320, 220, 120), second anti-reflective coating 5 30 (430, 330, 230), the first adhesive layer 540 (440, 340) and the second 5. The transparent substrate 550 (450) may have any of the corresponding characteristics described herein. obtain.

[0104] According to yet another embodiment, the third anti-reflective coating 680 has a particular thickness. For example, the third anti-reflective coating 680 may be at least about 50 nm, e.g. At least about 60 nm, or at least about 70 nm, or at least about 80 nm, or at least About 90 nm or at least about 100 nm or at least about 110 nm or at least about 12 0 nm or at least about 130 nm or at least about 140 nm or at least about 150 nm or at least about 160 nm or at least about 170 nm or at least about 180 nm The thickness of the thin film may be at least about 190 nm or at least about 200 nm. According to other embodiments, the anti-reflective coating 120 has a thickness of about 500 nm or less, such as about 490 nm or less, or about 480 nm or less, or about 470 nm or less, or about 460 nm or less, or about 450 nm or less, or about 440 nm or less, or about 430 nm or less, or about 420 nm or less, or about 410 nm or less, or about 400 nm or less, or about 390 nm or less, or about 380 nm or less, or 370 nm or less, or about 360 nm or less, or about 350 nm or less, or about 340 nm or less, or about 330 nm or less, or about 320 nm or less, or about 310 nm or less, or even about 300 nm or less The third anti-reflective coating 680 may have a thickness between the minimum and maximum values. It will be appreciated that the thickness of the third embodiment may be within a range of any of the above values. The anti-reflective coating 680 is between and at any of the minimum and maximum values ​​listed above. It is further recognized that the thickness of the layer may be any value, including

[0105] According to yet another embodiment, the third anti-reflective coating 680 has a specific ratio AC3 S iO2 / AC3 B AC3 SiO2 is the third anti-reflective coating 680 Percentage by weight of silica nanoparticles in the third antireflective coating 680 relative to the total weight AC3 is the concentration at Bis the total weight of the third antireflective coating 680, The weight percent of the first UV-curable acrylate binder in the third antireflective coating 680 For example, the third antireflective coating 680 has a concentration of at least about 0. 0.01, for example at least about 0.05 or at least about 0.07 or at least about 0.1 or at least about 0.12, or at least about 0.15, or at least about 0.17, or less at least about 0.20 or at least about 0.22 or at least about 0.25 or at least about A ratio AC3 of 0.27 or even at least about 0.30 SiO2 / AC3 B may have: According to yet other embodiments, the third antireflective coating 680 has a refractive index of about 1.3 or less, e.g. For example, about 1.2 or less, or about 1.1 or less, or about 1.0 or less, or about 0.9 or less, or about 0.8 or less, Ratio AC3 of about 0.7 or less, or about 0.6 or less, or even about 0.5 or less SiO2 / AC3 B The third anti-reflective coating 680 may have a value between the minimum and maximum values ​​given above, and Ratio AC3 in the range including any of those values SiO2 / AC3 B It is recognized that The third anti-reflective coating 680 is between the above minimum and maximum values ​​and Any value ratio AC3 including any of the values ​​above SiO2 / AC3 B It is recognized that can be.

[0106] According to yet another embodiment, the third anti-reflective coating 680 is a first UV curable According to yet another embodiment, a third anti-reflective coating may be included. The first UV-curable acrylate binder in 680 is SR351LV, SR355, S R399, Tetrafunctional acrylate monomer, Pentafunctional acrylate monomer, Pentaerythritol Thuritol tritetraacrylate (PETIA), Ebecry 140, Ebecr It can be yl 180, a multifunctional oligomer or a UV resin.

[0107] According to yet another embodiment, the third anti-reflective coating 680 is a first anti-reflective coating having a particular concentration. For example, the third anti-reflective coating 68 may include a UV-curable acrylate binder. 0 is at least about 40% by weight, for example at least about 50% by weight, based on the total weight of the first antireflective coating. At least about 42% by weight, or at least about 44% by weight, or at least about 46% by weight, or less at least about 48% by weight, or at least about 50% by weight, or at least about 52% by weight, or At least about 54% by weight, or at least about 56% by weight, or at least about 58% by weight, or even less The composition may have a first UV-curable acrylate binder concentration of at least about 60% by weight. According to an embodiment, the third anti-reflective coating 680 is a first anti-reflective coating about 95% by weight or less, for example about 93% by weight or less, or about 90% by weight or less, based on the total weight of about 88% by weight or less, or about 85% by weight or less, or about 83% by weight or less, or about 80% by weight or less, About 78% by weight or less, or about 75% by weight or less, or about 73% by weight or less, or even about 70% by weight or less The third antireflective coating may have a first UV-curable acrylate binder concentration below. 680 is the first value within the range between and including the above minimum and maximum values. It is recognized that the third anti-reflective coating may have a UV curable acrylate binder concentration of 1000 to 2000 nm. Any value between and including the above minimum and maximum values ​​may be used. It is further recognized that the first UV-curable acrylate binder concentration may have a value of

[0108] According to yet another embodiment, the third antireflective coating 680 includes a photoinitiator component. According to yet another embodiment, the photoinitiator composition in the third antireflective coating 680 may be Minutes: Omnirad 184, Omnirad 819, Omnirad 1173, It may be CPI 6976, other similar photoinitiators, or any combination of the above.

[0109] According to yet another embodiment, the third anti-reflective coating 680 has a specific concentration of optical aperture. For example, the third antireflective coating 680 may include an initiator component. At least about 2% by weight, for example at least about 2.2% by weight, based on the total weight of the coating. is at least about 2.5 wt.%, or at least about 2.7 wt.%, or at least about 3.0 wt.% % or at least about 3.2% by weight or at least about 3.5% by weight or at least about 3.7 % by weight or at least about 4.0% by weight or at least about 4.2% by weight or at least about 4 .5% by weight or at least about 4.7% by weight or at least about 5.0% by weight or at least The photoinitiator component may have a concentration of about 5.2% by weight or at least about 5.5% by weight. According to an embodiment, the third anti-reflective coating 680 is a first anti-reflective coating about 10% by weight or less, for example about 9.8% by weight or less or about 9.5% by weight or less, based on the total weight of or about 9.3% by weight or less, or about 9.0% by weight or less, or about 8.8% by weight or less, or about 8.5% by weight or less % by weight or less, or about 8.3% by weight or less, or about 8.0% by weight or less, or about 7.8% by weight or less, or about 7.5% by weight or less or about 7.3% by weight or less or about 7.0% by weight or less or about 6.8% by weight or less The third antireflective coating may have a photoinitiator component concentration of about 6.5% by weight or less. The range 680 is between and including any of the above minimum and maximum values. It will be appreciated that the third antireflective coating 680 may have a photoinitiator component concentration of Any value of the photoinitiator composition between and including any of the minimum and maximum values ​​listed above. It is further recognized that the composition may have a fractional concentration.

[0110] According to yet another embodiment, the third anti-reflective coating 680 is a silicon based coating having a specific concentration. For example, the third antireflective coating 680 may include nanoparticles. At least about 5% by weight, for example at least about 6% by weight, based on the total weight of the coating At least about 7% by weight, or at least about 8% by weight, or at least about 9% by weight, or or at least about 10% by weight, or at least about 11% by weight, or at least about 12% by weight, or at least About 13% by weight or at least about 14% by weight or at least about 15% by weight or at least about 16% by weight or at least about 17% by weight or at least about 18% by weight or at least about 1 9% by weight or at least about 20% by weight or at least about 21% by weight or at least about 22% by weight % by weight or at least about 23% by weight or at least about 24% by weight or even at least about According to another embodiment, the third anti-reflective coating may have a silica nanoparticle concentration of 25% by weight. The antireflective coating 680 is about 60% by weight or more based on the total weight of the first antireflective coating. For example, about 58% by weight or less, or about 55% by weight or less, or about 53% by weight or less, or about 50% by weight or less % or less by weight, or about 48% or less by weight, or about 45% or less by weight, or about 43% or less by weight, or about 40% or less by weight % or less, or about 38% or less, or about 35% or less, or about 33% or less, or even about 3 The third anti-reflective coating 680 may have a silica nanoparticle concentration of 0% or less by weight. Silica nanoparticles within a range between and including any of the minimum and maximum values ​​set forth above. It will be appreciated that the third anti-reflective coating 680 may have a concentration in excess of the above minimum values ​​and and a maximum silica nanoparticle concentration of any value between and including any of the values. It is further recognized that

[0111] According to yet another embodiment, the silica nanoparticles in the third antireflective coating 680 are According to another embodiment, the third anti-reflective coating may be a surface-treated silica nanoparticle. The silica nanoparticles in ring 680 can be generally solid, spherical silica nanoparticles.

[0112] According to yet another embodiment, the third anti-reflective coating 680 is a polysiloxane, It may be surface treated with an acrylate or a combination thereof.

[0113] According to another embodiment, the silica nanoparticles in the third antireflective coating 680 are For purposes of the embodiments described herein, the average particle size may be a specific average particle size (D50). The average particle size (D50) is measured according to ASTM E2490. The silica nanoparticles in the third antireflective coating 680 are at least about 1 nm, e.g. For example, at least about 2 nm, or at least about 3 nm, or at least about 4 nm, or at least about 5 nm or at least about 6 nm or at least about 7 nm or at least about 8 nm or less At least about 10 nm, or at least about 11 nm, or at least about 12 nm, or at least about 13 nm or at least about 14 nm or at least about 15 nm or at least about 16 nm Or may have an average particle size (D50) of at least about 17 nm, or at least about 18 nm. According to another embodiment, the silica nanoparticles in the third antireflective coating 680 are about 5 00 nm or less, for example, about 400 nm or less, or about 300 nm or less, or about 200 nm or less, About 100 nm or less, or about 95 nm or less, or about 90 nm or less, or about 85 nm or less, or about 80 nm or less, or about 75 nm or less, or about 65 nm or less, or about 60 nm or less, or about 55 nm or less or about 50 nm or less, or about 45 nm or less, or about 40 nm or less, or about 35 nm or less, or about 3 The third anti-reflective coating may have an average particle size (D50) of about 0 nm or less, or even about 25 nm or less. The silica nanoparticles in coating 680 are between and within the above minimum and maximum values. It is recognized that the average particle size (D50) may be within a range including any of the values. The silica nanoparticles in the anti-reflective coating 680 are between and including the minimum and maximum values ​​set forth above. It will be further recognized that the particle size may have any value, including any of the above values. can be.

[0114] According to another embodiment, the third anti-reflective coating 680 further comprises a slip agent. According to yet another embodiment, the slip agent may be included in a coating composition for use in the wet coating industry. Any known slip agent may be used, such as Tego glide 410, Tegora d 2100, Tegorad 2300, Tegorad 2500, BYK306, BYK307 and any combination thereof.

[0115] According to yet another embodiment, the third anti-reflective coating 680 is a specific concentration of slits. For example, the third antireflective coating 680 may include a coating material similar to that of the first antireflective coating. At least about 0.1% by weight, or at least about 0.5% by weight, or It may further have a slip agent concentration of at least about 1.0% by weight. For example, the third anti-reflective coating 680 is about 100% by weight of the total of the first anti-reflective coating. and having a slip agent concentration of about 5% by weight or less, or about 4.5% by weight or less, or about 4.0% by weight or less. The third anti-reflective coating 680 may have a reflectance between the minimum and maximum values ​​given above and therebetween. It will be appreciated that the slip agent concentration may be within a range including any of these values. The anti-reflective coating 680 may be any value between and including the minimum and maximum values ​​listed above. It will be further recognized that the slip agent concentration may be any value, including any of the above.

[0116] According to yet another embodiment, the third anti-reflective coating 680 further comprises a wetting agent. According to yet another embodiment, the wetting agent may be any of the agents used in the wet coating industry. known wetting agents such as BYK-377, BYK-UV 3500, Tego 270, Or any combination thereof.

[0117] According to yet another embodiment, the third anti-reflective coating 680 is a wetting agent having a specific concentration. For example, the third anti-reflective coating 680 may include a coating agent other than the first anti-reflective coating. At least about 0.01% by weight, or at least about 0.05% by weight, or According to yet another embodiment, the third humectant may have a wetting agent concentration of at least about 0.1% by weight. The anti-reflective coating 680 has a weight of about 0.3 with respect to the total weight of the first anti-reflective coating. % by weight or less, or about 0.25% by weight or less, or even about 0.2% by weight or less of a wetting agent concentration The third anti-reflective coating 680 has a reflectance between the minimum and maximum values ​​and between them. It will be appreciated that the slip agent concentration may be within a range including any of these values. The anti-reflection coating 680 may be any value between and including the minimum and maximum values ​​listed above. It is further recognized that the wetting agent concentration may be any value, including

[0118] According to another embodiment, the third anti-reflective coating 680 is a surface energy controlled According to yet another embodiment, the surface energy modifier is a wet Any known surface energy modifier used in the coating industry, e.g., BYK- 315, BYK-300, BYK-310, BY-378 or any combination thereof. do.

[0119] According to yet another embodiment, the third anti-reflective coating 680 has a surface area of ​​a particular concentration. For example, the third anti-reflective coating 680 may include an energy adjustment agent. At least about 0.01% by weight based on the total weight of the anti-glare coating or at least about 0. The surface energy modifier may have a concentration of at least about 0.05% by weight or at least about 0.1% by weight. According to another embodiment, the third anti-reflective coating 680 is a first anti-reflective coating. About 0.30% by weight or less, or about 0.25% by weight or less, or even about 0. The third antireflective coating 68 may have a surface energy modifier concentration of 2% by weight or less. 0 is the surface area between and including the minimum and maximum values ​​listed above. It will be appreciated that the third anti-reflective coating 680 may have an energy modifier concentration. , any value of surface energy between and including the above minimum and maximum values. It is further recognized that the composition may have an energy adjusting agent concentration.

[0120] According to yet another embodiment, the third anti-reflective coating 680 is a second UV curable According to yet another embodiment, a third UV-curable acrylate binder may be included. Acrylate binders include SR351LV, SR355, SR399, and tetrafunctional acrylates. Monomer, Pentafunctional Acrylate Monomer, Pentaerythritol Tritetraacrylate PETIA, Ebecryl 140, Ebecryl 180, Multifunctional Oligomers or UV resin.

[0121] According to yet another embodiment, the third anti-reflective coating 680 is a second anti-reflective coating having a particular concentration. For example, the third anti-reflective coating 68 may include a UV-curable acrylate binder. 0 is at least about 5.0 wt. % or less based on the total weight of the first antireflective coating at least about 7% by weight, or at least about 10% by weight, or at least about 12% by weight, or at least about 15% by weight, or at least about 17% by weight, or at least about 20% by weight, or at least about 22% by weight or even at least about 25% by weight of a second UV-curable acrylate binder; According to yet another embodiment, the third anti-reflective coating 680 may have a first about 60% by weight or less, or about 58% by weight or less, based on the total weight of the antireflective coating of about 55% by weight or less, or about 53% by weight or less, or about 50% by weight or less, or about 48% by weight or less, about 45% by weight or less, or about 43% by weight or less, or about 40% by weight or less of a second UV-curable acrylic The third antireflective coating 680 may have a binder concentration of at least one of the above minimums and A second UV-curable acrylate within a range between and including any of the maximum values. It will be appreciated that the third anti-reflective coating 680 may have a binder concentration of 0.1 to 0.5% by weight. A second UV curability of any value between and including the minimum and maximum values. It is further recognized that the composition may have an acrylate binder concentration.

[0122] FIG. 6b illustrates a portion of another exemplary composite film 601 according to embodiments described herein. As shown in FIG. 6b, the composite film 601 is formed on a first transparent substrate 61. 0, a first anti-reflective coating deposited on a first surface 612 of a first transparent substrate 610; 620, a second anti-reflective coating deposited on the second surface 614 of the first transparent substrate 610. The first anti-reflective coating 620 is laminated on the surface 622 of the first anti-reflective coating 620. Each repeating upper anti-reflective component 695 may include a first The first adhesive layer 640, the second transparent substrate 650 laminated to the first adhesive layer 640, and the second It may include a third anti-reflective coating 680 deposited on the transparent substrate 650 .

[0123] The number of repeating top anti-reflective elements 695 shown in FIG. 6b is exemplary and not limiting. It will be appreciated that, according to certain embodiments, multiple The composite film 601 has a certain number of repeating top layer components, for example at least three repeating top layers. Anti-reflective element 695 or at least four repeating upper anti-reflective elements 695 or at least At least five repeating upper anti-reflective elements 695 or at least six repeating upper anti-reflective structures The top anti-reflective element 695 or at least 8 repeating elements 695 or at least 7 repeating elements 100 or at least 900 repeating upper anti-reflective elements 695 or It may include 5 or at least 10 repeating top anti-reflective elements 695 .

[0124] According to certain embodiments, the composite film 601 may have a particular VLT. For example, The composite film 601 has a porosity of at least about 93.2%, such as at least about 93.4% or less. At least about 93.6%, or at least about 93.8%, or at least about 94.0%, or less At least about 94.2%, or at least about 94.4%, or at least about 94.6%, or less At least about 94.8%, or at least about 95.0%, or at least about 95.2%, or at least or at least about 95.4%, or at least about 95.6%, or at least about 95.8%, or even less According to yet another embodiment, the composite film 60 may have a VLT of at least about 96.0%. 1 may have a VLT of about 99.9% or less. It is recognized that a patient may have a VLT within a range between and including any of the above values. The composite film 601 may have any of the values ​​between the minimum and maximum values ​​listed above. It is further recognized that the VLT may have any value, including

[0125] According to yet other embodiments, the composite film 601 can have a particular haze value. For example, the composite film 601 has a film thickness of about 3% or less, such as about 2.9% or less, or about 2.8% or less, About 2.7% or less, or about 2.6% or less, or about 2.5% or less, or about 2.4% or less, or about 2.3% or less % or less, or about 2.2% or less, or about 2.1% or less, or about 2.0% or less, or about 1.9% or less, is about 1.8% or less, or about 1.7% or less, or about 1.6% or less, or about 1.5% or less, or about 1. The composite film 601 may have a haze value of 4% or less, or even about 1.3% or less. It will be appreciated that the composite film 601 may have a haze value within a range including any of the values. It is further understood that the haze value may be any value between and including any of the above values. It is recognized by others.

[0126] According to other embodiments, the composite film 601 may have a particular reflectance. For example, , the composite film 601 has a thickness of about 7.0% or less, for example, about 6.9% or less or about 6.8% or less. is about 6.7% or less, or about 6.6% or less, or about 6.5% or less, or about 6.4% or less, or about 6. 3% or less, or about 6.2% or less, or about 6.1% or less, or about 6.0% or less, or about 5.9% or less or about 5.8% or less, or about 5.7% or less, or about 5.6% or less, or about 5.5% or less, or about 5 0.4% or less, or about 5.3% or less, or about 5.2% or less, or about 5.1% or less, or about 5.0% or less The composite film 601 may have a reflectance between and including the minimum and maximum values ​​listed above. It will be appreciated that the composite film 60 may have a reflectance within a range including any of these values. Any value of reflectance between and including the minimum and maximum values ​​listed above. It is further recognized that the

[0127] According to embodiments described herein, the anti-reflective coatings described herein are Yarrod method, gravure method, reverse gravure method, mini gravure method, slot die method, spray Another layer, using a wet coating method such as a coating method or a dip coating method, For example, it may be applied to a substrate or another coating. According to the study, the newly applied coating was dried in an oven to remove the solvent. According to another embodiment, the dried coating is then exposed to UV light, electron beams, It can be cured by irradiation with laser or other high energy beam heating.

[0128] According to yet other embodiments, the pressure sensitive adhesive layers described herein can be applied by the Mayer rod method, the grating method, Ragavure method, reverse gravure method, mini gravure method, slot die method, spray coating method or The coating is applied to a substrate or another coating using a wet coating method such as a dip coating method. can be applied to.

[0129] Many different aspects and embodiments are possible. Some of the aspects and embodiments are described in the present specification. After reading this specification, those skilled in the art will understand that these aspects and embodiments are It is recognized that the following examples are merely illustrative and do not limit the scope of the present invention. Any one or more of the embodiments may be followed.

[0130] Embodiment 1. A first transparent substrate and a first reflector laminated on a first surface of the first transparent substrate. A composite film including an anti-reflective coating, the first anti-reflective coating comprising a first A UV-curable acrylate binder, a photoinitiator component, and a first anti-reflective coating are dispersed in the and a ratio AC1 of at least about 0.01 and not more than about 1.3. SiO2 / A C1 B Includes AC1 SiO2 is the weight of the first anti-reflective coating relative to the total weight of the first anti-reflective coating. is the concentration by weight percent of silica nanoparticles in the antireflective coating of AC1 B is the weight of the first antireflective coating relative to the total weight of the first antireflective coating. 1. Concentration in weight percent of the UV-curable acrylate binder, and the composite film has a haze value of about 3% or less. Composite film.

[0131] Embodiment 2. A first transparent substrate and a first reflector laminated on a first surface of the first transparent substrate. A composite film including an anti-reflective coating, the first anti-reflective coating comprising a first At least about 40% by weight and no more than about 95% by weight based on the total weight of the antireflective coating a first UV-curable acrylate binder having a concentration of a photoinitiator component at a concentration of at least about 2.0% by weight and no more than about 10% by weight, At least about 5% by weight and at least about 60% by weight based on the total weight of the antireflective coating. and a composite film comprising silica nanoparticles dispersed in the first antireflective coating at a concentration of and the composite film has a VLT of at least about 93.0% and a haze value of about 3% or less. A composite film having

[0132] Embodiment 3. At least about 93.2% or at least about 93.4% or at least about 9 3.6% or at least about 93.8% or at least about 94.0% or at least about 94 .2% or at least about 94.4% or at least about 94.6% or at least about 94. 8% or at least about 95.0% or at least about 95.2% or at least about 95.4 % or at least about 95.6% or at least about 95.8% or at least about 96.0% 3. The composite film of any one of claims 1 and 2, having a VLT of

[0133] Embodiment 4. About 3% or less, or about 2.9% or less, or about 2.8% or less, or about 2.7% or less, or is about 2.6% or less, or about 2.5% or less, or about 2.4% or less, or about 2.3% or less, or about 2. 2% or less, or about 2.1% or less, or about 2.0% or less, or about 1.9% or less, or about 1.8% or less or about 1.7% or less, or about 1.6% or less, or about 1.5% or less, or about 1.4% or less, or about 1 3. The composite film of any one of claims 1 and 2, having a haze value of .3% or less. .

[0134] Embodiment 5. About 7.0% or less, or about 6.9% or less, or about 6.8% or less, or about 6.7% or less or about 6.6% or less, or about 6.5% or less, or about 6.4% or less, or about 6.3% or less, or about 6.2% or less, or about 6.1% or less, or about 6.0% or less, or about 5.9% or less, or about 5.8% or less than about 5.7% or less than about 5.6% or less than about 5.5% or less than about 5.4% or A reflectance of about 5.3% or less, or about 5.2% or less, or about 5.1% or less, or about 5.0% or less. 3. The composite film according to any one of embodiments 1 and 2.

[0135] Embodiment 6. The first antireflective coating is at least about 50 nm or at least about 60 nm or at least about 70 nm or at least about 80 nm or at least about 90 nm or at least about 100 nm, or at least about 110 nm, or at least about 120 nm, or is at least about 130 nm, or at least about 140 nm, or at least about 150 nm, or At least about 160 nm or at least about 170 nm or at least about 180 nm or less 3. The method of claim 1, further comprising the step of: 13. The composite film according to claim 12 .

[0136] Embodiment 7. The first antireflective coating has a wavelength of about 500 nm or less or about 490 nm or less. or about 480 nm or less, or about 470 nm or less, or about 460 nm or less, or about 450 nm or less or about 440 nm or less, or about 430 nm or less, or about 420 nm or less, or about 410 nm or less or about 400 nm or less, or about 390 nm or less, or about 380 nm or less, or about 370 nm or less or about 360 nm or less, or about 350 nm or less, or about 340 nm or less, or about 330 nm or less or having a thickness of about 320 nm or less, or about 310 nm or less, or about 300 nm or less, 3. A composite film according to any one of aspects 1 and 2.

[0137] Embodiment 8. The first antireflective coating has a refractive index of at least about 0.01 or at least about 0 0.05 or at least about 0.07 or at least about 0.1 or at least about 0.12 or At least about 0.15, or at least about 0.17, or at least about 0.20, or Also about 0.22 or at least about 0.25 or at least about 0.27 or at least about 0. 30 ratio AC1 SiO2 / AC1 B Includes AC1 SiO2 The first anti-reflective coating The weight percentage of silica nanoparticles in the first antireflective coating relative to the total weight of the coating. The concentration in the AC1 B is the weight of the first anti-reflective coating relative to the total weight of the first anti-reflective coating. The weight percent of the first UV-curable acrylate binder in the antireflective coating is 3. The composite film of any one of embodiments 1 and 2, wherein

[0138] Embodiment 9. The first antireflective coating has an average refractive index of about 1.3 or less, or about 1.2 or less, or about 1. 1 or less, or about 1.0 or less, or about 0.9 or less, or about 0.8 or less, or about 0.7 or less, or about 0. Ratio AC1 of 6 or less or about 0.5 or lessSiO2 / AC1 B Includes AC1 SiO2 But the first of silica nanoparticles in the first antireflective coating relative to the total weight of the antireflective coating. is the concentration of particles in weight percent, AC1 B The total weight of the first anti-reflective coating is weight of the first UV-curable acrylate binder in the first antireflective coating relative to the amount of 3. The composite film of any one of embodiments 1 and 2, wherein the concentration is in percent by amount.

[0139] Embodiment 10. First UV-curable acrylate binder in the first antireflective coating However, SR351LV, SR355, SR399, tetrafunctional acrylate monomers, pentafunctional Acrylate Monomer, Pentaerythritol Tritetraacrylate (PETIA) , Ebecryl 140, Ebecryl 180, multifunctional oligomer or UV resin 3. The composite film of any one of embodiments 1 and 2, comprising

[0140] Embodiment 11. The first anti-reflective coating comprises a first anti-reflective coating having a total weight of At least about 40% by weight, or at least about 42% by weight, or at least about 44% by weight % by weight or at least about 46% by weight or at least about 48% by weight or at least about 50% by weight % or at least about 52% by weight or at least about 54% by weight or at least about 56% by weight or at least about 58% by weight or at least about 60% by weight of the first UV-curable acrylic acid. 3. The composite film of any one of the preceding claims, comprising a lylate binder.

[0141] Embodiment 12. The first anti-reflective coating comprises a first anti-reflective coating having a total weight of about 95% by weight or less, about 93% by weight or less, about 90% by weight or less, or about 88% by weight or less than about 85% by weight, or less than about 83% by weight, or less than about 80% by weight, or less than about 78% by weight or less than about 75% by weight, or less than about 73% by weight, or less than about 70% by weight. V. The composite filler according to any one of embodiments 1 and 2, comprising a curable acrylate binder. Room.

[0142] Embodiment 13. The photoinitiator component in the first antireflective coating is Omnirad 1 84, Omnirad 819, Omnirad 1173, CPI 6976, and other similar 3. The complex according to any one of embodiments 1 and 2, comprising a photoinitiator such as a Composite film.

[0143] Embodiment 14. The first antireflective coating comprises a first antireflective coating having a total weight of at least about 2% by weight, or at least about 2.2% by weight, or at least about 2.5% by weight % by weight or at least about 2.7% by weight or at least about 3.0% by weight or at least about 3. 2% by weight or at least about 3.5% by weight or at least about 3.7% by weight or at least about 4.0% by weight or at least about 4.2% by weight or at least about 4.5% by weight or at least or at least about 4.7% by weight, or at least about 5.0% by weight, or at least about 5.2% by weight, or less 3. Any one of embodiments 1 and 2, comprising a photoinitiator component at a concentration of at least about 5.5% by weight. The composite film described herein.

[0144] Embodiment 15. The first antireflective coating comprises a first antireflective coating having a total weight of about 10% by weight or less, about 9.8% by weight or less, about 9.5% by weight or less, or about 9.3% by weight or less % by weight or less, or about 9.0% by weight or less, or about 8.8% by weight or less, or about 8.5% by weight or less, About 8.3% by weight or less, or about 8.0% by weight or less, or about 7.8% by weight or less, or about 7.5% by weight or less than about 7.3% by weight, or less than about 7.0% by weight, or less than about 6.8% by weight, or less than about 6. 3. The composition of any one of claims 1 and 2, comprising a photoinitiator component at a concentration of 5% by weight or less. Composite film.

[0145] Embodiment 16. The first antireflective coating comprises a first antireflective coating having a total weight of at least about 5% by weight, or at least about 6% by weight, or at least about 7% by weight, At least about 8% by weight, or at least about 9% by weight, or at least about 10% by weight, or less At least about 11% by weight, or at least about 12% by weight, or at least about 13% by weight, or or at least about 14% by weight, or at least about 15% by weight, or at least about 16% by weight, or at least about 17% by weight or at least about 18% by weight or at least about 19% by weight or at least about 20% by weight or at least about 21% by weight or at least about 22% by weight or at least about 2 Silica nanoparticles at a concentration of 3% by weight or at least about 24% by weight or at least about 25% by weight 3. The composite film of any one of embodiments 1 and 2, comprising a child.

[0146] Embodiment 17. The first antireflective coating comprises a first antireflective coating having a total weight of about 60% by weight or less, about 58% by weight or less, about 55% by weight or less, or about 53% by weight or less than about 50% by weight or less than about 48% by weight or less than about 45% by weight or less than about 43% by weight or less than about 40% by weight or less than about 38% by weight or less than about 35% by weight or less than about 33% by weight Any of embodiments 1 and 2, comprising silica nanoparticles at a concentration of less than or equal to about 30% by weight. 1. A composite film according to claim 1.

[0147] Embodiment 18. The silica nanoparticles in the first antireflective coating are surface-treated silica nanoparticles. 3. The antireflective coating of embodiment 2, wherein the antireflective coating is a nanoparticle.

[0148] Embodiment 19. The silica nanoparticles in the first antireflective coating are polysiloxane, The antireflective coating of embodiment 18, which is surface-treated with an acrylate or a combination thereof. Ting.

[0149] Embodiment 20. The silica nanoparticles in the first antireflective coating are generally solid silica 3. The composite film of any one of embodiments 1 and 2, wherein the nanoparticles are nanoparticles.

[0150] Embodiment 21. The silica nanoparticles in the first antireflective coating have a particle size of at least about 1n m or at least about 2 nm or at least about 3 nm or at least about 4 nm or at least or at least about 5 nm, or at least about 6 nm, or at least about 7 nm, or at least about 8 nm, or At least about 10 nm, or at least about 11 nm, or at least about 12 nm, or at least or at least about 13 nm, or at least about 14 nm, or at least about 15 nm, or at least about 16 nm or at least about 17 nm or at least about 18 nm 3. A composite film according to any one of embodiments 1 and 2.

[0151] Embodiment 22. The silica nanoparticles in the first antireflective coating are about 500 nm or less. or about 400 nm or less, or about 300 nm or less, or about 200 nm or less, or about 100 nm or less, about 95 nm or less, or about 90 nm or less, or about 85 nm or less, or about 80 nm or less, or about 75 nm or less, or about 65 nm or less, or about 60 nm or less, or about 55 nm or less, or about 50 nm or less or about 45 nm or less, or about 40 nm or less, or about 35 nm or less, or about 30 nm or less, or about 2 3. The complex according to any one of embodiments 1 and 2, having an average particle size (D50) of 5 nm or less. Composite film.

[0152] Embodiment 23. The method of embodiment 1 or 2, wherein the first antireflective coating comprises a slip agent. 13. The composite film according to claim 12 .

[0153] 24. The slip agent is Tego glide 410 or Tegorad 210 0, Tegorad 2300, Tegorad 2500, BYK306, BYK30 24. The composite film of embodiment 23, including 7 and any combination thereof.

[0154] Embodiment 25. The first antireflective coating comprises a total weight of the first antireflective coating 24. The composition of claim 23, further comprising a slip agent at a concentration of at least about 0.01% by weight of the composition. Composite film.

[0155] Embodiment 26. The first antireflective coating comprises a first antireflective coating having a total weight of 24. The composite film of embodiment 23, comprising a slip agent at a concentration of about 5% by weight or less. .

[0156] Embodiment 27. Any of embodiments 1 and 2, wherein the first antireflective coating comprises a wetting agent. The composite film according to any one of claims 1 to 5.

[0157] Embodiment 28. The wetting agent is BYK-377, BYK-UV 3500, Tego 27 28. The composite film of embodiment 27, comprising:

[0158] Embodiment 29. The first antireflective coating comprises a total weight of the first antireflective coating 28. The composite of embodiment 27, comprising a wetting agent at a concentration of at least about 0.01% by weight of film.

[0159] Embodiment 30. The first antireflective coating comprises a total weight of the first antireflective coating 28. The composite film of embodiment 27, comprising a wetting agent at a concentration of about 0.3% by weight or less. .

[0160] Embodiment 31. An embodiment in which the first antireflective coating comprises a surface energy modifier 3. A composite film according to any one of 1 and 2.

[0161] Embodiment 32. The surface energy modifier is BYK-315, BYK-300, BYK- 31, BY-310, BY-378, or any combination thereof. .

[0162] Embodiment 33. The first antireflective coating comprises a total weight of the first antireflective coating 3. A surface energy modifier at a concentration of at least about 0.01% by weight of 1. The composite film according to claim 1.

[0163] Embodiment 34. The first antireflective coating comprises a first antireflective coating having a total weight of As described in embodiment 31, the surface energy modifier is present in a concentration of about 0.3% by weight or less. Composite film.

[0164] Embodiment 35. A first antireflective coating comprising a second UV-curable acrylate binder. 3. The composite film of any one of embodiments 1 and 2, comprising

[0165] Embodiment 36. The second UV-curable acrylate binder is SR351LV, SR355 , SR399, tetrafunctional acrylate monomer, pentafunctional acrylate monomer, penta Erythritol tritetraacrylate (PETIA), Ebecry 140, Ebe 36. The composite of embodiment 35, comprising cryl 180, a multifunctional oligomer, or a UV resin. film.

[0166] Embodiment 37. The first antireflective coating comprises a total weight of the first antireflective coating and a second UV-curable acrylate binder at a concentration of at least about 5.0% by weight. 36. The composite film of embodiment 35.

[0167] Embodiment 38. The first antireflective coating comprises a total weight of the first antireflective coating and a second UV-curable acrylate binder at a concentration of about 60% by weight or less. 36. The composite film according to embodiment 35.

[0168] Embodiment 39. Any one of the preceding embodiments, wherein the first transparent substrate comprises a PET film. The composite film according to claim 1.

[0169] Embodiment 40. The preceding embodiment, wherein the first transparent substrate comprises an optically transparent PET film. 13. The composite film according to claim 12 .

[0170] Embodiment 41. The first transparent substrate comprises a single layer of optically transparent PET film. 13. The composite film according to any one of the embodiments.

[0171] Embodiment 42. The PET film has a thickness of at least about 5 mils or at least about 6 mils or less. At least about 7 mils or at least about 8 mils or at least about 9 mils or at least about 10 42. The composite film of any one of embodiments 39, 40, and 41, including its thickness in mils.

[0172] Embodiment 43. The PET film has a thickness of about 15 mils or less, or about 14 mils or less, or about 13 mils or less. 12 mils or less, or about 11 mils or less. 13. The composite film according to claim 12 .

[0173] Embodiment 44. A composite film comprising a first UV-curable acrylate binder, a photoinitiator component and a second antireflective coating comprising silica nanoparticles dispersed in the second antireflective coating. 2. The composite film of any one of the preceding embodiments, further comprising a coating.

[0174] Embodiment 45. A second anti-reflective coating is deposited on the second surface of the first transparent substrate. The second surface of the first transparent substrate is parallel and opposite to the first surface of the first transparent substrate. 45. The composite film of embodiment 44.

[0175] Embodiment 46. The second antireflective coating is at least about 50 nm or at least About 60 nm or at least about 70 nm or at least about 80 nm or at least about 90 nm m or at least about 100 nm or at least about 110 nm or at least about 120 nm or at least about 130 nm, or at least about 140 nm, or at least about 150 nm, or is at least about 160 nm, or at least about 170 nm, or at least about 180 nm, or 46. ​​The method of claim 45, having a thickness of at least about 190 nm or at least about 200 nm. Composite film.

[0176] Embodiment 47. The second antireflective coating has a wavelength of about 500 nm or less or about 490 nm or less. or about 480 nm or less, or about 470 nm or less, or about 460 nm or less, or about 450 nm or less or about 440 nm or less, or about 430 nm or less, or about 420 nm or less, or about 410 nm or less or about 400 nm or less, or about 390 nm or less, or about 380 nm or less, or about 370 nm or less or about 360 nm or less, or about 350 nm or less, or about 340 nm or less, or about 330 nm or less or less than about 320 nm, or less than about 310 nm, or less than about 300 nm. 46. ​​The composite film of embodiment 45.

[0177] Embodiment 48. The second antireflective coating has a reflective index of at least about 0.01 or at least about 0.05 or at least about 0.07 or at least about 0.1 or at least about 0.12 or is at least about 0.15, or at least about 0.17, or at least about 0.20, or less At least about 0.22 or at least about 0.25 or at least about 0.27 or at least about 0 .30 Ratio AC2 SiO2 / AC2 B Including AC2 SiO2 But the second anti-reflective coating The weight percentage of silica nanoparticles in the second antireflective coating relative to the total weight of the coating. The concentration in the AC2 B is the weight of the second anti-reflective coating relative to the total weight of the second anti-reflective coating. The weight percent of the second UV-curable acrylate binder in the antireflective coating is 46. ​​The composite film of embodiment 45, wherein

[0178] Embodiment 49. The second antireflective coating has an average refractive index of about 1.3 or less, or about 1.2 or less, or about 1 0.1 or less, or about 1.0 or less, or about 0.9 or less, or about 0.8 or less, or about 0.7 or less, or about 0 Ratio AC2 of .6 or less or about 0.5 or less SiO2 / AC2 BIncluding AC2 SiO2 But, The weight of silica nanoparticles in the second antireflective coating relative to the total weight of the second antireflective coating. is the concentration of nanoparticles in weight percent, AC2 B The total reflection of the second anti-reflective coating is of the second UV-curable acrylate binder in the second antireflective coating by weight 46. ​​The composite film of embodiment 45, wherein the concentration is in weight percent.

[0179] Embodiment 50. The UV-curable acrylate in the second binder antireflective coating is S R351LV, SR355, SR399, tetrafunctional acrylate monomer, pentafunctional acrylate Lylate Monomer, Pentaerythritol Tritetraacrylate (PETIA), Eb Including ecry 140, Ebecryl 180, multifunctional oligomers or UV resins, 46. ​​The composite film of embodiment 45.

[0180] Embodiment 51. The second antireflective coating comprises a total weight of the second antireflective coating at least about 40% by weight, or at least about 42% by weight, or at least about 44% by weight % or at least about 46% by weight or at least about 48% by weight or at least about 50% by weight or at least about 52% by weight, or at least about 54% by weight, or at least about 56% by weight, or The first UV-curable acrylic acid is present in a concentration of at least about 58% by weight or at least about 60% by weight. 46. ​​The composite film of embodiment 45, comprising a polymerizable binder.

[0181] Embodiment 52. The second antireflective coating comprises a total weight of the second antireflective coating about 95% by weight or less, about 93% by weight or less, about 90% by weight or less, or about 88% by weight or less than about 85% by weight, or less than about 83% by weight, or less than about 80% by weight, or less than about 78% by weight or less than about 75% by weight, or less than about 73% by weight, or less than about 70% by weight. 46. ​​The composite film of embodiment 45, comprising a curable acrylate binder.

[0182] Embodiment 53. The photoinitiator component in the second antireflective coating is Omnirad 1 84, Omnirad 819, Omnirad 1173, CPI 6976, and other similar 46. ​​The composite film of embodiment 45, comprising a photoinitiator such as, or any combination thereof.

[0183] Embodiment 54. The second antireflective coating comprises a total weight of the second antireflective coating at least about 2% by weight, or at least about 2.2% by weight, or at least about 2.5% by weight % by weight or at least about 2.7% by weight or at least about 3.0% by weight or at least about 3. 2% by weight or at least about 3.5% by weight or at least about 3.7% by weight or at least about 4.0% by weight or at least about 4.2% by weight or at least about 4.5% by weight or at least or at least about 4.7% by weight, or at least about 5.0% by weight, or at least about 5.2% by weight, or less 46. ​​The composite film of embodiment 45, comprising a photoinitiator component at a concentration of at least about 5.5% by weight. .

[0184] Embodiment 55. The second antireflective coating comprises a total weight of the second antireflective coating about 10% by weight or less, about 9.8% by weight or less, about 9.5% by weight or less, or about 9.3% by weight or less % by weight or less, or about 9.0% by weight or less, or about 8.8% by weight or less, or about 8.5% by weight or less, About 8.3% by weight or less, or about 8.0% by weight or less, or about 7.8% by weight or less, or about 7.5% by weight or less than about 7.3% by weight, or less than about 7.0% by weight, or less than about 6.8% by weight, or less than about 6. 46. ​​The composite film of embodiment 45, comprising a photoinitiator component at a concentration of 5% by weight or less.

[0185] Embodiment 56. The second antireflective coating comprises a total weight of the second antireflective coating at least about 5% by weight, or at least about 6% by weight, or at least about 7% by weight, At least about 8% by weight, or at least about 9% by weight, or at least about 10% by weight, or less At least about 11% by weight, or at least about 12% by weight, or at least about 13% by weight, or or at least about 14% by weight, or at least about 15% by weight, or at least about 16% by weight, or at least about 17% by weight or at least about 18% by weight or at least about 19% by weight or at least about 20% by weight or at least about 21% by weight or at least about 22% by weight or at least about 2 Silica nanoparticles at a concentration of 3% by weight or at least about 24% by weight or at least about 25% by weight 46. ​​The composite film of embodiment 45, comprising a polymerizable compound.

[0186] Embodiment 57. The second antireflective coating comprises a total weight of the second antireflective coating about 60% by weight or less, about 58% by weight or less, about 55% by weight or less, or about 53% by weight or less than about 50% by weight or less than about 48% by weight or less than about 45% by weight or less than about 43% by weight or less than about 40% by weight or less than about 38% by weight or less than about 35% by weight or less than about 33% by weight 46. ​​The composite film of embodiment 45, comprising silica nanoparticles at a concentration of about 30% by weight or less. Film.

[0187] Embodiment 58. The silica nanoparticles in the second antireflective coating are surface-treated silica nanoparticles. 46. ​​The composite film of embodiment 45, wherein the particle is a nanoparticle.

[0188] Embodiment 59. The silica nanoparticles in the second antireflective coating are selected from the group consisting of polysiloxane, 59. The antireflective coating of embodiment 58, which is surface-treated with an acrylate or a combination thereof. Ting.

[0189] Embodiment 60. The silica nanoparticles in the second antireflective coating are generally solid silica 46. ​​The composite film of embodiment 45, wherein the nanoparticles are nanoparticles.

[0190] Embodiment 61. The silica nanoparticles in the second antireflective coating have a molecular weight of at least about 1n m or at least about 2 nm or at least about 3 nm or at least about 4 nm or at least or at least about 5 nm, or at least about 6 nm, or at least about 7 nm, or at least about 8 nm, or At least about 10 nm, or at least about 11 nm, or at least about 12 nm, or at least or at least about 13 nm, or at least about 14 nm, or at least about 15 nm, or at least about 16 nm or at least about 17 nm or at least about 18 nm 46. ​​The composite film of embodiment 45.

[0191] Embodiment 62. The silica nanoparticles in the second antireflective coating are about 500 nm or less. or about 400 nm or less, or about 300 nm or less, or about 200 nm or less, or about 100 nm or less or about 95 nm or less, or about 90 nm or less, or about 85 nm or less, or about 80 nm or less, or about 7 5 nm or less, or about 65 nm or less, or about 60 nm or less, or about 55 nm or less, or about 50 nm or less or about 45 nm or less, or about 40 nm or less, or about 35 nm or less, or about 30 nm or less, or about 46. ​​The composite film of embodiment 45, having an average particle size (D50) of 25 nm or less.

[0192] Embodiment 63. As described in embodiment 45, the second antireflective coating comprises a slip agent. Composite film.

[0193] 64. The slip agent is Tego glide 410, Tegorad 210 0, Tegorad 2300, Tegorad 2500, BYK306, BYK30 7, and any combination thereof.

[0194] Embodiment 65. The second antireflective coating is a total weight of the first antireflective coating. 64. The composition of claim 63, further comprising a slip agent at a concentration of at least about 0.01% by weight of the composition. Composite film.

[0195] Embodiment 66. The first antireflective coating comprises a first antireflective coating having a total weight of 64. The composite film of embodiment 63, comprising a slip agent at a concentration of about 5% by weight or less. .

[0196] Embodiment 67. The composite of embodiment 45, wherein the second antireflective coating comprises a wetting agent. Composite film.

[0197] Embodiment 68. The wetting agent is BYK-377, BYK-UV 3500, Tego 27 68. The composite film of embodiment 67, comprising 0 or any combination thereof.

[0198] Embodiment 69. The second antireflective coating comprises a total weight of the second antireflective coating 68. The composite of embodiment 67, comprising a wetting agent at a concentration of at least about 0.01% by weight of film.

[0199] Embodiment 70. The second antireflective coating comprises a total weight of the second antireflective coating 68. The composite film of embodiment 67, comprising a wetting agent at a concentration of about 0.3% by weight or less. .

[0200] Embodiment 71. An embodiment in which the second antireflective coating comprises a surface energy modifier 46. ​​The composite film according to claim 45.

[0201] Embodiment 72. The surface energy modifier is BYK-315, BYK-300, BYK- 310, BY-378, or any combination thereof. .

[0202] Embodiment 73. The second antireflective coating comprises a total weight of the second antireflective coating 8. The composition of claim 7, further comprising a surface energy modifier at a concentration of at least about 0.01% by weight of the composition. 1. The composite film according to claim 1.

[0203] Embodiment 74. The second antireflective coating comprises a total weight of the second antireflective coating As described in embodiment 71, the surface energy modifier is present in a concentration of about 0.3% by weight or less. Composite film.

[0204] Embodiment 75. The second antireflective coating comprises a second UV-curable acrylate binder. 46. ​​The composite film of embodiment 45, comprising

[0205] Embodiment 76. The second UV-curable acrylate binder is SR351LV, SR355 , SR399, tetrafunctional acrylate monomer, pentafunctional acrylate monomer, penta Erythritol tritetraacrylate (PETIA), Ebecry 140, Ebe 76. The composite of embodiment 75, comprising cryl 180, a multifunctional oligomer or a UV resin. film.

[0206] Embodiment 77. The second antireflective coating comprises a total weight of the second antireflective coating and a second UV-curable acrylate binder at a concentration of at least about 5.0% by weight. 76. The composite film of embodiment 75.

[0207] Embodiment 78. The second antireflective coating comprises a total weight of the second antireflective coating and a second UV-curable acrylate binder at a concentration of about 60% by weight or less. 76. The composite film according to embodiment 75.

[0208] Embodiment 79. A composite film is a first adhesive laminated to a surface of a first anti-reflective film. 2. The composite film of any one of the preceding embodiments, further comprising an adhesive layer.

[0209] Embodiment 80. The first adhesive layer is made of Aroset 1452, A manufactured by Ashland roset 1450, Aroset 6428, Duro-Tak 222A, Dur 80. The composite film of embodiment 79, comprising o-Tak 80-1093 or a combination thereof. .

[0210] Embodiment 81. The method of embodiment 79, wherein the first adhesive layer has a thickness of at least about 1 μm. The composite film described herein.

[0211] Embodiment 82. As described in embodiment 79, wherein the first adhesive layer has a thickness of about 50 μm or less. Composite film.

[0212] Embodiment 83. The composite film of embodiment 79, wherein the first adhesive layer comprises nanoparticles. .

[0213] Embodiment 84. An embodiment in which the nanoparticles of the first adhesive layer comprise surface-treated silica nanoparticles. 84. The composite film according to embodiment 83.

[0214] Embodiment 85. The nanoparticles in the first adhesive layer are at least about 1 nm or at least about 2 nm or at least about 3 nm or at least about 4 nm or at least about 5 nm or less At least about 6 nm, or at least about 7 nm, or at least about 8 nm, or at least about 10 nm m or at least about 11 nm or at least about 12 nm or at least about 13 nm or less At least about 14 nm, or at least about 15 nm, or at least about 16 nm, or at least 84. The method according to claim 83, having an average particle size (D50) of about 17 nm or at least about 18 nm. Composite film.

[0215] Embodiment 86. The nanoparticles in the first adhesive layer are about 500 nm or less or about 400 nm or less. or about 300 nm or less, about 200 nm or less, about 100 nm or less, or about 95 nm or less or about 90 nm or less, or about 85 nm or less, or about 80 nm or less, or about 75 nm or less, or about 6 5 nm or less, or about 60 nm or less, or about 55 nm or less, or about 50 nm or less, or about 45 nm or less or less than about 40 nm or less than about 35 nm or less than about 30 nm or less than about 25 nm 84. The composite film of embodiment 83, having a particle size (D50).

[0216] Embodiment 87. A composite film further comprising a second transparent substrate laminated to the first adhesive layer. 4. The composite film of any one of the preceding embodiments.

[0217] Embodiment 88. The composite film of embodiment 87, wherein the second transparent substrate comprises a PET film. Film.

[0218] Embodiment 89. The second transparent substrate comprises an optically transparent PET film. The composite film according to claim 1.

[0219] Embodiment 90. An embodiment in which the second transparent substrate comprises a single layer of optically transparent PET film. 88. The composite film according to embodiment 87.

[0220] Embodiment 91. The second transparent substrate is at least about 1 mil or at least about 2 mils or less Embodiments including a thickness of at least about 3 mils, or at least about 4 mils, or at least about 5 mils. 88. The composite film according to embodiment 87.

[0221] Embodiment 92. The second transparent substrate is about 15 mils or less, or about 14 mils or less, or about 13 mils or less. 88. The composite film of embodiment 87, comprising a thickness of about 12 mils or less, or about 11 mils or less. Film.

[0222] Embodiment 93. A composite film having a second adhesive layer laminated to the surface of a second transparent substrate. 2. The composite film of any one of the preceding embodiments, further comprising:

[0223] Embodiment 94. The second adhesive layer is made of Aroset 1452, A manufactured by Ashland. roset 1450, Aroset 6428, Duro-Tak 222A, Dur 94. The composite film of embodiment 93, comprising o-Tak 80-1093 or a combination thereof. .

[0224] Embodiment 95. The method of embodiment 93, wherein the second adhesive layer has a thickness of at least about 1 μm. The composite film described herein.

[0225] Embodiment 96. The method of embodiment 93, wherein the second adhesive layer has a thickness of about 50 μm or less. Composite film.

[0226] Embodiment 97. The composite film of embodiment 93, wherein the second adhesive layer comprises nanoparticles. .

[0227] Embodiment 98. An embodiment in which the nanoparticles of the second adhesive layer comprise surface-treated silica nanoparticles. 94. The composite film according to embodiment 93.

[0228] Embodiment 99. The nanoparticles in the second adhesive layer are at least about 1 nm or at least about 2 nm or at least about 3 nm or at least about 4 nm or at least about 5 nm or less At least about 6 nm, or at least about 7 nm, or at least about 8 nm, or at least about 10 nm m or at least about 11 nm or at least about 12 nm or at least about 13 nm or less At least about 14 nm, or at least about 15 nm, or at least about 16 nm, or at least 94. The method according to claim 93, having an average particle size (D50) of about 17 nm or at least about 18 nm. Composite film.

[0229] Embodiment 100. The nanoparticles in the second adhesive layer are about 500 nm or less or about 400 nm or less. or less than about 300 nm or less than about 200 nm or less than about 100 nm or less than about 95 nm or about 90 nm or less, or about 85 nm or less, or about 80 nm or less, or about 75 nm or less, or about 65 nm or less, or about 60 nm or less, or about 55 nm or less, or about 50 nm or less, or about 45 nm or less than about 40 nm or less than about 35 nm or less than about 30 nm or less than about 25 nm 94. The composite film of embodiment 93, having an average particle size (D50).

[0230] Embodiment 101. A composite film is laminated on the surface of a second transparent substrate to form a third anti-reflective The third antireflective coating is a first UV-curable acrylic coating. The photoinitiator component and the silica nanoparticles dispersed in the second antireflective coating. 94. The composite film of embodiment 93, comprising a second antireflective coating comprising a

[0231] Embodiment 102. The third antireflective coating is at least about 50 nm or at least At least about 60 nm, or at least about 70 nm, or at least about 80 nm, or at least about 90 nm or at least about 100 nm or at least about 110 nm or at least about 120 nm m or at least about 130 nm or at least about 140 nm or at least about 150 nm or at least about 160 nm, or at least about 170 nm, or at least about 180 nm, or has a thickness of at least about 190 nm or at least about 200 nm, The composite film according to claim 1.

[0232] Embodiment 103. The third antireflective coating has a reflectance of about 500 nm or less or about 490 nm or less. or less than about 480 nm or less than about 470 nm or less than about 460 nm or less than about 450 nm or less than about 440 nm or less than about 430 nm or less than about 420 nm or less than about 410 nm or less than about 400 nm or less than about 390 nm or less than about 380 nm or less than about 370 nm or less than about 360 nm or less than about 350 nm or less than about 340 nm or less than about 330 nm or less than about 320 nm, or less than about 310 nm, or less than about 300 nm; 102. The composite film of embodiment 101.

[0233] Embodiment 104. The third antireflective coating has a reflectance of at least about 0.01 or at least About 0.05 or at least about 0.07 or at least about 0.1 or at least about 0.12 or at least about 0.15, or at least about 0.17, or at least about 0.20, or less at least about 0.22 or at least about 0.25 or at least about 0.27 or at least about Ratio AC3 of 0.30 SiO2 / AC3 B Includes AC3 SiO2 But the third anti-reflective coating The weight percentage of silica nanoparticles in the third antireflective coating relative to the total weight of the coating. Concentration in cents, AC3 B is the weight of the third anti-reflective coating relative to the total weight of the third anti-reflective coating. The weight percent of the third UV-curable acrylate binder in the antireflective coating of 102. The composite film of embodiment 101, wherein the concentration of

[0234] Embodiment 105. The third antireflective coating has a refractive index of about 1.3 or less, or about 1.2 or less, or about 1.1 or less, or about 1.0 or less, or about 0.9 or less, or about 0.8 or less, or about 0.7 or less, or about Ratio AC3 of 0.6 or less or about 0.5 or less SiO2 / AC3 B Includes AC3 SiO2 but, Silica in the third antireflective coating relative to the total weight of the third antireflective coating is the concentration of nanoparticles in weight percent, AC3 B But the third anti-reflective coating the third UV-curable acrylate binder in the third antireflective coating by weight 102. The composite film of embodiment 101, wherein the concentration in weight percent is

[0235] Embodiment 106. The UV-curable acrylate binder in the third antireflective coating comprises: SR351LV, SR355, SR399, tetrafunctional acrylate monomer, pentafunctional acrylate Acrylate Monomer, Pentaerythritol Tritetraacrylate (PETIA), E Contains becry 140, Ebecryl 180, multifunctional oligomers or UV resins 102. The composite film of embodiment 101.

[0236] Embodiment 107. The third antireflective coating has a total weight of the third antireflective coating At least about 40% by weight, or at least about 42% by weight, or at least about 44% by weight % by weight or at least about 46% by weight or at least about 48% by weight or at least about 50% by weight % or at least about 52% by weight or at least about 54% by weight or at least about 56% by weight or at least about 58% by weight or at least about 60% by weight of the first UV-curable acrylic acid. 102. The composite film of embodiment 101, comprising a lylate binder.

[0237] Embodiment 108. The third antireflective coating has a total weight of the third antireflective coating about 95% by weight or less, about 93% by weight or less, about 90% by weight or less, or about 88% by weight or less % or less by weight, or about 85% or less by weight, or about 83% or less by weight, or about 80% or less by weight, or about 78% or less by weight % or less, or about 75% or less, or about 73% or less, or about 70% or less by weight 102. The composite film of embodiment 101, comprising a UV-curable acrylate binder.

[0238] Embodiment 109. The photoinitiator component in the third antireflective coating is Omnirad 184, Omnirad 819, Omnirad 1173, CPI 6976, other 102. The composite film of embodiment 101, comprising a similar photoinitiator or any combination thereof.

[0239] Embodiment 110. The third antireflective coating has a total weight of the third antireflective coating At least about 2% by weight, or at least about 2.2% by weight, or at least about 2.5% by weight % by weight or at least about 2.7% by weight or at least about 3.0% by weight or at least about 3 .2% by weight or at least about 3.5% by weight or at least about 3.7% by weight or at least About 4.0% by weight or at least about 4.2% by weight or at least about 4.5% by weight or less At least about 4.7% by weight, or at least about 5.0% by weight, or at least about 5.2% by weight, or 102. The composite fiber of embodiment 101, comprising a photoinitiator component at a concentration of at least about 5.5% by weight. Room.

[0240] Embodiment 111. The third antireflective coating has a total weight of the third antireflective coating About 10% by weight or less, or about 9.8% by weight or less, or about 9.5% by weight or less, or about 9. 3% by weight or less, or about 9.0% by weight or less, or about 8.8% by weight or less, or about 8.5% by weight or less, about 8.3% by weight or less, or about 8.0% by weight or less, or about 7.8% by weight or less, or about 7.5% by weight or less % or less, or about 7.3% by weight or less, or about 7.0% by weight or less, or about 6.8% by weight or less, or about 6 102. The composite film of embodiment 101, comprising a photoinitiator component at a concentration of .5% by weight or less.

[0241] Embodiment 112. The third antireflective coating has a total weight of the third antireflective coating At least about 5% by weight, or at least about 6% by weight, or at least about 7% by weight, At least about 8% by weight, or at least about 9% by weight, or at least about 10% by weight, or less at least about 11% by weight, or at least about 12% by weight, or at least about 13% by weight, or At least about 14% by weight, or at least about 15% by weight, or at least about 16% by weight, or or at least about 17% by weight, or at least about 18% by weight, or at least about 19% by weight, or at least about 20% by weight or at least about 21% by weight or at least about 22% by weight or at least about Silica nanoparticles at a concentration of 23% by weight, or at least about 24% by weight, or at least about 25% by weight. 102. The composite film of embodiment 101, comprising particles.

[0242] Embodiment 113. The third antireflective coating has a total weight of the third antireflective coating about 60% by weight or less, about 58% by weight or less, about 55% by weight or less, or about 53% by weight or less % or less by weight, or about 50% or less by weight, or about 48% or less by weight, or about 45% or less by weight, or about 43% or less by weight % or less by weight, or about 40% or less by weight, or about 38% or less by weight, or about 35% or less by weight, or about 33% or less by weight 102. The method of claim 101, further comprising the step of: Composite film.

[0243] Embodiment 114. The silica nanoparticles in the third antireflective coating are surface-treated silica 102. The composite film of embodiment 101, wherein the nanoparticles are nanoparticles.

[0244] Embodiment 115. The silica nanoparticles in the third antireflective coating are selected from the group consisting of polysiloxane 102. The composite fiber of embodiment 101, which is surface-treated with a tertiary acrylate, an acrylate, or a combination thereof. Room.

[0245] Embodiment 116. The silica nanoparticles in the third antireflective coating are generally solid silica. 102. The composite film of embodiment 101, wherein the nanoparticles are kaolin nanoparticles.

[0246] Embodiment 117. The silica nanoparticles in the third antireflective coating have a density of at least about 1 nm or at least about 2 nm or at least about 3 nm or at least about 4 nm or less At least about 5 nm, or at least about 6 nm, or at least about 7 nm, or at least about 8 nm, is at least about 10 nm, or at least about 11 nm, or at least about 12 nm, or At least about 13 nm, or at least about 14 nm, or at least about 15 nm, or at least about 1 6 nm or at least about 17 nm or at least about 18 nm average particle size (D50) 102. The composite film of embodiment 101.

[0247] Embodiment 118. The silica nanoparticles in the third antireflective coating are about 500 nm or less. or less than about 400 nm, or less than about 300 nm, or less than about 200 nm, or less than about 100 nm or about 95 nm or less, or about 90 nm or less, or about 85 nm or less, or about 80 nm or less, or about 75 nm or less, or about 65 nm or less, or about 60 nm or less, or about 55 nm or less, or about 50 nm or less than about 45 nm or less than about 40 nm or less than about 35 nm or less than about 30 nm or 102. The composite film of embodiment 101, having an average particle size (D50) of about 25 nm or less.

[0248] Embodiment 119. Any of embodiments 1 and 2, wherein the third antireflective coating comprises a wetting agent. 2. The composite film according to claim 1 .

[0249] Embodiment 120. The wetting agent is BYK-377, BYK-UV 3500, Tego 2 70, or any combination thereof.

[0250] Embodiment 121. The third antireflective coating has a total weight of the third antireflective coating 120. The method of claim 119, further comprising the step of: Composite film.

[0251] Embodiment 122. The third antireflective coating has a total weight of the third antireflective coating As described in embodiment 119, the composition further comprises a wetting agent at a concentration of at least about 0.3% by weight or less. Composite film.

[0252] Embodiment 123. The third antireflective coating comprises a surface energy modifier. 3. The composite film according to any one of aspects 1 and 2.

[0253] Embodiment 124. The surface energy modifier is BYK-315, BYK-300, BYK 124. The composite filler of embodiment 123, comprising BY-310, BY-378, or any combination thereof. Room.

[0254] Embodiment 125. The third antireflective coating has a total weight of the third antireflective coating In embodiments, the surface energy modifier is present in a concentration of at least about 0.01% by weight of the composition. 123. A composite film according to claim 123.

[0255] Embodiment 126. The third antireflective coating has a total weight of the third antireflective coating 124. The method of claim 123, further comprising the step of: The composite film described herein.

[0256] Embodiment 127. The third antireflective coating comprises a second UV-curable acrylate binder. 3. The composite film of any one of embodiments 1 and 2, comprising:

[0257] Embodiment 128. The second UV-curable acrylate binder is SR351LV, SR35 5, SR399, tetrafunctional acrylate monomer, pentafunctional acrylate monomer, pen Taerythritol tritetraacrylate (PETIA), Ebecry 140, Eb As described in embodiment 127, comprising ecryl 180, a multifunctional oligomer, or a UV resin. Composite film.

[0258] Embodiment 129. The third antireflective coating has a total weight of the third antireflective coating A second UV-curable acrylate binder at a concentration of at least about 5.0% by weight based on the amount of the 128. The composite film of embodiment 127.

[0259] Embodiment 130. The third antireflective coating has a total weight of the third antireflective coating The second UV-curable acrylate binder is present in a concentration of about 60% by weight or less. 128. The composite film of claim 127.

[0260] Embodiment 131. A method of forming a composite film, comprising: Providing a formulation, the first anti-reflective coating formulation having a first reflective At least about 0.4% by weight and at least about 5.5% by weight based on the total weight of the protective coating formulation. % of the raw material first UV-curable acrylate binder component, first anti-reflective coating A concentration of at least about 0.2% by weight and no more than about 2.0% by weight based on the total weight of the formulation. a small amount of raw photoinitiator component, based on the total weight of the first antireflective coating formulation, % by weight and less than or equal to about 1.9% by weight of silica nanoparticles. applying a first antireflective coating formulation to a transparent substrate; and The coating formulation is dried to form a first antireflective coating on the transparent substrate. forming a composite film comprising at least about 93.0% VLT and the composite film has a haze value of about 3% or less.

[0261] Embodiment 132. The step of applying the first antireflective coating formulation comprises using a Meyer Rod method, gravure method, dip coating method, slot die method and other coating methods 132. The method of embodiment 131, comprising applying the coating using a method.

[0262] Embodiment 133. The step of drying the antireflective coating formulation comprises drying the antireflective coating formulation in an oven. The coating is dried and then photo-treated using UV light, an electron beam, or other high energy light. 132. The method of embodiment 131, comprising curing the coating by applying a heat-treating agent to the coating.

[0263] example The concepts described herein are further described in the following examples, which are set forth in the appended claims. It is not intended to limit the scope of the invention as claimed.

[0264] Example 1 Eleven sample composite films S1-S11 were prepared according to the embodiments described herein. Successful.

[0265] The first sample composite film S1 was mixed in a methyl ethyl ketone (MEK) solution. The anti-reflective coating solution described herein was prepared by preparing the following ingredients: The raw material components were: 1) 3.10 parts by weight of surface-treated silicon 1) 1.1 parts by weight of trimethylpropane nanoparticles (Nanobyk 3650 dispersion), and 96.52 parts by weight of 1-methoxy-2-propanol. 1) UV-curable acrylate binder and 3) 0.28 parts by weight of photoinitiator (10.00% solids) The anti-reflective coating solution was applied to #3 Meyer's A rod is used to coat one side of a 7 mil SH38 PET film and heated at 110°C. The dried coating was then cured with UV light. The first anti-reflective coating was formed on the PET film by the same method. The coating solution was applied to a 7 mil SH38 PET film using a #3 Meyer rod. (SKC Film, Korea) on the second side and place in a 110°C oven for 30 s. The dried coating was then cured with UV light to form a PET film. A second anti-reflective coating was then formed on the

[0266] The second sample composite film S2 was prepared by mixing the following ingredients in a methyl ethyl ketone solution: The present invention can be applied to the present invention by preparing an anti-reflective coating solution containing the components. The raw material components were: 1) 4.00 parts by weight of surface-treated silica nanoparticles; (Nanobyk 3650 dispersion), 2) 0.08 parts by weight of trimethylpropane trimethylazoline acrylate) and 75.00 parts by weight of 1-methoxy-2-propanol. V Curable acrylate binder, 3) 20.00 parts by weight of propylene glycol monomethyl Ether acetate solvent and 4) 0.20 parts by weight of photoinitiator (10.00% solids CP I 6976 in MEK). Apply the anti-reflective coating solution to a #3 Meyer rod. 7 mil SH38 PET film was coated on one side with The dried coating was then cured with UV light to give a P A first anti-reflective coating was formed on the ET film. Then, the same anti-reflective coating was applied to the ET film. The coating solution was applied to a second strip of 7 mil SH38 PET film using a #3 Meyer rod. The surface was coated with 110°C and dried in an oven for 30 seconds. The coating is cured with UV light to create a second anti-reflective coating on the PET film. Formed.

[0267] The third sample composite film S3 was prepared by mixing the raw materials in a methyl ethyl ketone solution. According to the embodiments described herein, an antireflective coating solution comprising The raw material components were: 1) 2.7 parts by weight of surface-treated silica nanoparticles (Nan OBYK 3650 dispersion), 2) 1.2 parts by weight of trimethylpropane triacrylate and 95.8 parts by weight of 1-methoxy-2-propanol. 3) 0.30 parts by weight of photoinitiator (10.00% solids CPI 6976) The anti-reflective coating solution was applied to the 7 mm well using a #3 Meyer rod. Coat one side of SH38 PET film and heat in oven at 110℃ for 30 seconds. The dried coating was then cured with UV light to form a PET film. The first antireflective coating was then formed on the substrate. The same antireflective coating solution was then added to the substrate. Coat the second side of a 7 mil SH38 PET film using a #3 Meyer rod. The coating was then dried in an oven at 110°C for 30 seconds. A second anti-reflective coating was formed on the PET film upon curing with UV light.

[0268] The fourth sample composite film S4 was prepared by mixing the following materials in a methyl ethyl ketone solution: The present invention can be applied to the present invention by preparing an anti-reflective coating solution containing the components. The raw material components were: 1) 2.34 parts by weight of surface-treated silica nanoparticles; (Nanobyk 3650 dispersion), 2) 1.30 parts by weight of trimethylpropane trimethylsilyl The first UV-curable polymer contained acrylate and 96.04 parts by weight of 1-methoxy-2-propanol. Curable acrylate binder and 3) 0.32 parts by weight of photoinitiator (10.00% solids CPI The anti-reflective coating solution was applied to a #3 Mayer rod. Coat one side of 7 mil SH38 PET film using a 110°C oven. The dried coating was then cured with UV light to give a PE A first anti-reflective coating was formed on the T film. The coating solution was applied to a second strip of 7 mil SH38 PET film using a #3 Meyer rod. The coated surface was dried in an oven at 110°C for 30 seconds. The coating is then cured with UV light to form a second anti-reflective coating on the PET film. Successful.

[0269] The fifth sample composite film S5 was prepared by mixing the following ingredients in a methyl ethyl ketone solution: The present invention can be applied to the present invention by preparing an anti-reflective coating solution containing the components. The raw material components were 1.97 parts by weight of surface-treated silica nanoparticles (N anobyk 3650 dispersion), 2) 1.40 parts by weight of trimethylpropane triacrylate The first UV cured 3) 0.35 parts by weight of photoinitiator (10.00% solids CPI 6 Anti-reflective coating solution (containing 976 in MEK solution) was applied using a #3 Meyer rod. Then, coat one side of a 7 mil SH38 PET film and heat in a 110°C oven. It was allowed to dry for 30 seconds. The dried coating was then cured with UV light to form a PET film. A first anti-reflective coating was formed on the film. Then, the same anti-reflective coating was applied to the film. Apply the solution to the second side of a 7 mil SH38 PET film using a #3 Meyer rod. The coated film was dried in an oven at 110°C for 30 seconds. The coating is then cured with UV light to form a second anti-reflective coating on the PET film. Ta.

[0270] The sixth sample composite film S6 was prepared by mixing the following materials in a methyl ethyl ketone solution: The present invention can be applied to the present invention by preparing an anti-reflective coating solution containing the components. The raw material components were 0.80 parts by weight of surface-treated silica nanoparticles (N anobyk 3650 dispersion), 2) 1.80 parts by weight of trimethylpropane triacrylate The first UV cured 3) 0.45 parts by weight of photoinitiator (10.00% solids CPI 6 Anti-reflective coating solution (containing 976 in MEK solution) was applied using a #3 Meyer rod. Then, coat one side of a 7 mil SH38 PET film and heat in a 110°C oven. It was allowed to dry for 30 seconds. The dried coating was then cured with UV light to form a PET film. A first anti-reflective coating was formed on the film. Then, the same anti-reflective coating was applied to the film. Apply the solution to the second side of a 7 mil SH38 PET film using a #3 Meyer rod. The coated film was dried in an oven at 110°C for 30 seconds. The coating is then cured with UV light to form a second anti-reflective coating on the PET film. Ta.

[0271] The seventh sample composite film S7 was prepared by mixing the following materials in a methyl ethyl ketone solution: The present invention can be applied to the present invention by preparing an anti-reflective coating solution containing the components. The raw material components were 1.20 parts by weight of surface-treated silica nanoparticles (N anobyk 3650 dispersion), 2) 1.60 parts by weight of trimethylpropane triacrylate The first UV cured 3) 0.40 parts by weight of photoinitiator (10.00% solids CPI 6 Anti-reflective coating solution (containing 976 in MEK solution) was applied using a #3 Meyer rod. Then, coat one side of a 7 mil SH38 PET film and heat in a 110°C oven. It was allowed to dry for 30 seconds. The dried coating was then cured with UV light to form a PET film. A first anti-reflective coating was formed on the film. Then, the same anti-reflective coating was applied to the film. Apply the solution to the second side of a 7 mil SH38 PET film using a #3 Meyer rod. The coated film was dried in an oven at 110°C for 30 seconds. The coating is then cured with UV light to form a second anti-reflective coating on the PET film. Ta.

[0272] The eighth sample composite film S8 was prepared by mixing the following materials in a methyl ethyl ketone solution: The present invention can be applied to the present invention by preparing an anti-reflective coating solution containing the components. The raw material components were 1.60 parts by weight of surface-treated silica nanoparticles (N anobyk 3650 dispersion), 2) 1.50 parts by weight of trimethylpropane triacrylate The first UV cured 3) 0.38 parts by weight of photoinitiator (10.00% solids CPI 6 Anti-reflective coating solution (containing 976 in MEK solution) was applied using a #3 Meyer rod. Then, coat one side of a 7 mil SH38 PET film and heat in a 110°C oven. It was allowed to dry for 30 seconds. The dried coating was then cured with UV light to form a PET film. A first anti-reflective coating was formed on the film. Then, the same anti-reflective coating was applied to the film. Apply the solution to the second side of a 7 mil SH38 PET film using a #3 Meyer rod. The coated film was dried in an oven at 110°C for 30 seconds. The coating is then cured with UV light to form a second anti-reflective coating on the PET film. Ta.

[0273] The ninth sample composite film was prepared by mixing the following raw materials in a methyl ethyl ketone solution: The embodiments described herein can be achieved by preparing an antireflective coating solution comprising The raw material components were 1.20 parts by weight of surface-treated silica nanoparticles (Nan OBYK 3650 dispersion), 2) 1.60 parts by weight of trimethylpropane triacrylate and 95.80 parts by weight of propylene glycol monomethyl ether acetate, 1) a UV-curable acrylate binder; 2) 0.20 parts by weight of a slip agent (10.00% 2) 1.20 parts by weight of a photoinitiator ( Anti-reflective coating solution containing 10.00% solids CPI 6976 in MEK. , coated one side of 7 mil SH38 PET film using a #3 Meyer rod. The dried coating was then applied to a U-shaped The first anti-reflective coating was then formed on the PET film by curing with V light. The same anti-reflective coating solution was applied to a 7 mil SH38 film using a #3 Meyer rod. The second side of the PET film was coated and dried in an oven at 110°C for 30 seconds. The dried coating is then cured with UV light to form a second reverse layer on the PET film. An anti-reflection coating was formed.

[0274] The tenth sample composite film S10 is the same as the ninth sample composite film S9. The antireflective coating solution described herein can be prepared as described in The anti-reflective coating solution was applied using a #3 Meyer rod. The film was coated on one side of a 7 mil SH38 PET film and placed in a 110°C oven for 3 The dried coating was then cured with UV light to form a PET film. A first anti-reflective coating was formed on the film. The liquid was then coated onto the second side of a 7 mil SH38 PET film using a #3 Meyer rod. The coated plate was then dried in an oven at 110°C for 30 seconds. The coating was cured with UV light to form a second anti-reflective coating on the PET film. The same anti-reflective coating solution as described in S9 was applied to 2 mils of the coating solution according to the procedure described above. Melinex 453 PET film (DuPont) coated on both sides, The first pressure sensitive adhesive (PSA) coating (8.3% solids Arose 1452 in MEK and toluene) was applied to an AR-coated 2 mil PET film. A PSA coating thickness of approximately 4.0 μm was applied to one side of the film (110° C. oven). Dry for 2 minutes). The first AR-coated 7 mil PET film was then The first PSA coat of coated 2 mil Melinex 453 PET film The coating was laminated.

[0275] The eleventh sample composite film S11 is the same as the ninth sample composite film S9. The antireflective coating solution described herein can be prepared as described in The anti-reflective coating solution was applied using a #3 Meyer rod. The film was coated on one side of a 7 mil SH38 PET film and placed in a 110°C oven for 3 The dried coating was then cured with UV light to form a PET film. A first anti-reflective coating was formed on the film. The liquid was then coated onto the second side of a 7 mil SH38 PET film using a #3 Meyer rod. The coated plate was then dried in an oven at 110°C for 30 seconds. The coating was cured with UV light to form a second anti-reflective coating on the PET film. The same anti-reflective coating solution as described in S9 was applied to 2 mils of the coating solution according to the procedure described above. Melinex 453 PET film (DuPont) coated on both sides, UV cured (2 sheets of AR coated 2 mil Melinex 453 PE The first pressure sensitive adhesive (PSA) (Ar 8.3% solids) A coating of Oset 1452 in MEK and toluene was applied to the first AR coating. A PSA coating thickness of approximately 4.0 μm was applied to one side of a 2 mil PET film that had been pre-treated. (Dried in oven at 110°C for 2 minutes). Then, the first AR-coated 7 mm The PET film was coated with 2 mil Melinex 453 PE The first PSA coating of T film was laminated to create a 9 mil composite film. A second PSA (8.3% solids solution of Aroset 1452 in MEK and toluene) was added. The second is a 2-mil AR-coated Melinex 453 PET film. The 9 mil A was then applied to one side of the second sheet (dried in a 110°C oven for 2 minutes). Laminate the 2 mil side of the R-coated composite film onto the second PSA coating. did.

[0276] Three comparative sample composite films, CS1-CS3, were formed.

[0277] The first comparative sample composite film CS1 was mixed in a methyl ethyl ketone solution. The anti-reflective coating solution was prepared by preparing the following raw material components: 1) 4.7 parts by weight of surface-treated silica nanoparticles (Nanobyk 3650 dispersion) 2) 0.6 parts by weight of trimethylpropane triacrylate and 94.55 parts by weight of 1) a UV-curable acrylate binder comprising 1-methoxy-2-propanol; and 2) Contains 0.15 parts by weight of photoinitiator (10.00% solids CPI 6976 in MEK). Anti-reflective coating solution was applied to 7 mil SH38 PET using a #3 Meyer rod. The film was coated on one side and dried in an oven at 110° C. for 30 seconds. The dried coating was cured with UV light to form the first anti-reflective coating on the PET film. The same anti-reflective coating solution was then applied to a #3 Meyer rod. The second side of the 7 mil SH38 PET film was coated with 110°C heat. The dried coating was then cured with UV light to A second anti-reflective coating was formed on the PET film.

[0278] The second comparative sample composite film CS2 was mixed in a methyl ethyl ketone solution. The anti-reflective coating solution was prepared by preparing the following raw material components: 1) 5.0 parts by weight of surface-treated silica nanoparticles (Nanobyk 3650 dispersion) 2) 0.50 parts by weight of trimethylpropane triacrylate and 94.37 parts by weight of A first UV-curable acrylate binder containing 1-methoxy-2-propanol and 3 ) 0.13 parts by weight of photoinitiator (10.00% solids CPI 6976 in MEK) The anti-reflective coating solution was applied to 7 mil SH38 PE using a #3 Meyer rod. The coating was applied to one side of the T film and dried in an oven at 110°C for 30 seconds. The dried coating was then cured with UV light to form a first anti-reflective coating on the PET film. The same anti-reflective coating solution was then applied to a #3 Meyer rod. Coat the second side of a 7 mil SH38 PET film using a 110°C The dried coating was then cured with UV light. , a second anti-reflective coating was formed on the PET film.

[0279] The third comparative sample composite film CS3 is similar to the ninth comparative sample composite film S9. By preparing the antireflective coating solution as described herein, The anti-reflective coating solution was applied using a #3 Meyer rod. Then, coat one side of a 7 mil SH38 PET film and heat in a 110°C oven. It was allowed to dry for 30 seconds. The dried coating was then cured with UV light to form a PET film. A first anti-reflective coating was formed on the film. Then, the same anti-reflective coating was applied to the film. Apply the solution to the second side of a 7 mil SH38 PET film using a #3 Meyer rod. The coated film was dried in an oven at 110°C for 30 seconds. The coating is then cured with UV light to form a second anti-reflective coating on the PET film. The first pressure sensitive adhesive (PSA) (8.3% solids Aroset 1452 in MEK and (solution in toluene) coating on 2 mil Melinex 453 PET film. Applied to one side (dried in oven at 110°C for 2 minutes). Then the first AR coating The 7 mil PET film was coated with 2 mil Melinex 453 PET film. Laminated to the first PSA coating.

[0280] Sample composite films S1 to S8 and comparative sample composite films CS1 and CS2 The composition of each dry antireflective coating is summarized in Table 1 below. [Table 1]

[0281] Sample composite films S1 to S8 and comparative sample composite films CS1 and CS2 are The visible light transmittance (VLT) and haze values ​​were measured by BYK Gardner. The measurement results of the haze value are summarized in Table 2 below. [Table 2]

[0282] Not all of the tasks described in the general description or examples above are required, and certain tasks may require Some may not be necessary, and one or more tasks may be performed in addition to the tasks listed. Additionally, the order in which the operations are presented is not necessarily the order in which the operations should be performed.

[0283] Benefits, other advantages, and solutions to problems have been described above with regard to specific embodiments. , advantage, solution to a problem, or benefit, advantage or solution that may give rise to or be made more pronounced Any feature of the present invention that is essential, necessary, or essential to any or all of the claims is not included in the present specification. It should not be considered a feature.

[0284] The specification and illustrations of the embodiments set forth herein are provided to provide a general understanding of the structure of the various embodiments. The specification and examples are intended to provide a method for using the structures or methods described herein. It is intended to serve as an exhaustive and comprehensive description of all of the elements and features of the devices and systems It is not intended that separate embodiments may also be provided in combination in a single embodiment. Conversely, various features that are, for brevity, described in the context of a single embodiment, may also be used separately or in the context of a single embodiment. Further, references to values ​​stated in ranges are intended to include the entire range. Numerous other embodiments will become apparent to those of skill in the art only after reading this specification. Structural, logical substitutions, or other changes may be made without departing from the scope of this disclosure. Other embodiments may be used and derived therefrom, as may be made without departing from the spirit and scope of the present invention. Accordingly, the present disclosure is to be regarded as illustrative rather than restrictive. It should be.

Claims

1. A first transparent substrate; and a composite including a first anti-reflective coating disposed on a first surface of the first transparent substrate; A film, the first antireflective coating comprising: a first UV curable acrylate binder; A photoinitiator component, silica nanoparticles dispersed in the first antireflective coating; and A ratio AC1 of at least about 0.01 and not more than about 1.3 SiO2 / AC1 B Including AC1 SiO2 is the weight of the first anti-reflective coating relative to the total weight of the first anti-reflective coating is the concentration of the silica nanoparticles in the coating in weight percent; AC1 B However, The weight of the first antireflective coating relative to the total weight of the first antireflective coating. is the concentration in weight percent of the first UV curable acrylate binder; the composite film having a VLT of at least about 93.0%; The composite film, wherein the composite film has a haze value of about 3% or less.

2. A first transparent substrate; and a first anti-reflective coating disposed on a first surface of the first transparent substrate; A composite film, the first antireflective coating comprising: At least about 40% by weight and at least about 9% by weight based on the total weight of the first antireflective coating. a first UV curable acrylate binder at a concentration of 5% by weight or less; at least about 2.0 wt. % and about a photoinitiator component at a concentration of 10% by weight or less; and At least about 5% by weight and about 60% by weight based on the total weight of the first antireflective coating. % by weight or less of silica nanoparticles dispersed in said first antireflective coating. fruit, the composite film having a VLT of at least about 93.0%; The composite film, wherein the composite film has a haze value of about 3% or less.

3. The first antireflective coating has a thickness of at least about 50 nm and no more than about 500 nm.

3. The composite film of claim 1 having a thickness of 100 nm to 150 nm.

4. The first antireflective coating has a ratio A of at least about 0.01 and not more than about 1.

3. C1 SiO2 / AC1 B Including AC1 SiO2 of the first anti-reflective coating The weight percentage of the silica nanoparticles in the first antireflective coating relative to the total weight is the concentration in the AC1 B is based on the total weight of the first antireflective coating. The weight percent of the first UV-curable acrylate binder in the first antireflective coating 3. The composite film of claim 2, wherein the concentration is in percent.

5. The first UV curable acrylate binder in the first antireflective coating is R351LV, SR355, SR399, tetrafunctional acrylate monomer, pentafunctional acrylate acrylate monomer, pentaerythritol tritetraacrylate (PETIA), Eb Ebecryl 140, Ebecryl 180, multifunctional oligomers or UV resins; 3. A composite film according to claim 1 or 2.

6. the first anti-reflective coating comprises, based on a total weight of the first anti-reflective coating, and a concentration of at least about 40% by weight and no more than about 95% by weight of said first UV-curable acrylic acid. The composite film of claim 1 comprising a binder.

7. The photoinitiator component in the first antireflective coating is Omnirad 184, Omnirad 819, Omnirad 1173, CPI 6976 and other similar lights The composite film according to any one of claims 1 and 2, comprising an initiator or any combination thereof. Hmm.

8. the first anti-reflective coating comprises, based on a total weight of the first anti-reflective coating, 10. The method of claim 1, further comprising: The composite film according to claim 1.

9. The silica nanoparticles in the first antireflective coating are surface treated silica nanoparticles.

3. The antireflective coating of claim 1 , wherein

10. The silica nanoparticles in the first antireflective coating are polysiloxane, acrylic 10. The antireflective coating of claim 9, which is surface treated with a fluorine-containing polymer, a fluorine-containing amine, a fluorine-containing phosphate, or a combination thereof.

11. The silica nanoparticles in the first antireflective coating are generally solid silica nanoparticles.

3. The composite film of claim 1 , wherein the polymerizable compound is a tertiary amine.

12. The silica nanoparticles in the first antireflective coating are at least about 1 nm and 3. The method according to claim 1, having an average particle size (D50) of about 500 nm or less. Composite film.

13. The first anti-reflective coating comprises a second UV-curable acrylate binder. Item 3. The composite film according to any one of items 1 and 2.

14. the first anti-reflective coating comprises, based on a total weight of the first anti-reflective coating, and a concentration of at least about 5.0% by weight and no more than about 60% by weight of said second UV curable acrylic.

14. The composite film of claim 13, comprising a late binder.

15. 1. A method of forming a composite film, comprising: Providing a first antireflective coating formulation, said first antireflective coating formulation comprising: The coating formulation comprises: At least about 0.4 wt. %, based on the total weight of the first antireflective coating formulation. and a first UV curable acrylate binder component of the raw material at a concentration of about 5.5% by weight or less; At least about 0.2 wt. %, based on the total weight of the first antireflective coating formulation. and a raw photoinitiator component at a concentration of about 2.0% by weight or less; and At least about 0.7 wt. %, based on the total weight of the first antireflective coating formulation. and silica nanoparticles at a concentration of about 1.9% by weight or less; applying the first anti-reflective coating formulation to a transparent substrate; and The anti-reflective coating formulation is dried to form a first reflective coating layer deposited on the transparent substrate. forming a composite film including an anti-static coating; the composite film having a VLT of at least about 93.0%; The method of claim 1, wherein the composite film has a haze value of about 3% or less.

Citation Information

Patent Citations

  • Anti-reflection film, and coating liquid of ultraviolet light-curable resin material composition

    JP2010196014A

  • Antireflection film

    JP2011154177A

  • Antireflection film, antireflective polarizing plate and transmissive liquid crystal display

    JP2013076969A

  • Reflection preventing body, electrostatic capacity type touch panel, and display device with electrostatic capacity type touch panel

    JP2013083903A

  • Composition for anti-reflective coatings that provides improved scratch resistance, anti-reflective film using the same, and method for manufacturing the same.

    JP2014529763A